Resin composition and film
By using resin compositions with specific heat resistance with specific structures and appropriate amounts of additives, the problem of heat -degradation of additives in existing technologies at high temperatures is solved, and higher thermal resistance and functional stability are achieved.
Patent Information
- Application Number
- CN202180042688.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-02-18
- Filing Date
- 2021-06-11
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-06-11
AI Technical Summary
The conventional resin composition is prone to thermal deterioration of additives at high temperatures, resulting in insufficient function and promoting deterioration of resin.
Use resin compositions containing a high heat resistance resin with a specific part of the structure. By adding additives below 50 % to less than 50 % of the resin, the content of the specific duplicate unit in the resin is more than 2 Moor % and 50 Moore % %. , To inhibit the deterioration of additives.
Effectively suppress the degradation of additives, improves the heat resistance of the resin composition, and maintain its functional performance in various purposes.
Smart Images

Figure CN115885011B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition and a film. Background Art
[0002] Thermoplastic resins such as polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyvinyl acetate, polyurethane, acrylonitrile butadiene styrene resin, and acrylic resin are commonly used in various daily necessities or industrial products because of their good processability. Thermoplastic resins are used, for example, in photolithography resists in the field of semiconductor manufacturing (see, for example, Patent Documents 1 to 3, etc.), gas barrier laminated films that protect packaged items from gas intrusion as packaging materials (see, for example, Patent Documents 4 to 9, etc.), and hard coating films used as protective films for liquid crystal polarizers, etc. (see, for example, Patent Documents 10 to 12, etc.).
[0003] On the other hand, these common resins have low heat resistance and are therefore difficult to use in applications requiring heat resistance. Instead of these common resins, resins with high melting points such as engineering plastics and super engineering plastics are sometimes used. However, these engineering plastics have poor processability and low solubility in general organic solvents, so they have the disadvantage of being difficult to use in thin film applications such as coating films.
[0004] In addition, when using a resin, various additives are usually mixed into the resin for purposes such as improving processability or improving weather resistance, thereby preparing a resin composition for use. Therefore, the additive also needs to have heat resistance that can fully withstand the processing temperature or use temperature of the resin composition. In order to improve the heat resistance of the additive, for example, Patent Documents 13 to 15 disclose a technology for increasing the molecular weight of the additive.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2020 / 066806
[0008] Patent Document 2: Japanese Patent Application Publication No. 2005-234534
[0009] Patent Document 3: Japanese Patent Application Publication No. 2010-181730
[0010] Patent Document 4: Japanese Patent Publication No. 63-28017
[0011] Patent Document 5: Japanese Patent Application Publication No. 2004-106443
[0012] Patent Document 6: Japanese Patent Application Publication No. 2007-69456
[0013] Patent Document 7: Japanese Patent Application Publication No. 2002-36419
[0014] Patent Document 8: Japanese Patent No. 2556940
[0015] Patent Document 9: Japanese Patent No. 2790054
[0016] Patent Document 10: Japanese Patent Application Laid-Open No. 1-086101
[0017] Patent Document 11: Japanese Patent Application Laid-Open No. 4-338901
[0018] Patent Document 12: Japanese Patent Application Laid-Open No. 61-247743
[0019] Patent Document 13: Japanese Patent Application Laid-Open No. 10-338777
[0020] Patent Document 14: Japanese Patent Application Publication No. 2003-40937
[0021] Patent Document 15: International Publication No. 2008 / 062860 Summary of the invention
[0022] Technical problem to be solved by the invention
[0023] As mentioned above, various additives have been developed to improve heat resistance, but at high temperatures, the additives will decompose to a certain extent, making it difficult to fully exert their functions. Furthermore, the thermal decomposition products of the additives often promote the degradation of the resin. Under such circumstances, it is expected to develop a resin composition that meets the high heat resistance requirements in recent years.
[0024] Therefore, an object of the present invention is to provide a resin composition which can suppress thermal degradation of additives and can be used in various applications, and a film comprising the resin composition.
[0025] Means for solving technical problems
[0026] The present inventors have conducted intensive studies and have developed the present invention by using a resin composition containing a specific resin having excellent heat resistance.
[0027] The present invention is described as follows, for example.
[0028] [1] A resin composition comprising a resin R having a repeating unit having a partial structure represented by the following general formula (I) or (II).
[0029] [Chemical structure 1]
[0030]
[0031] In formula (I), Q A The ester bond shown in the formula, R A represents a substituent, n1 represents an integer of 1 to 5, * represents a bonding site to the remainder of the above repeating unit, and ** represents a bonding site to the phenyl group in the formula.
[0032] [Chemical structure 2]
[0033]
[0034] In formula (II), Q B represents the difference between Q in formula (I) A A linking group other than an ester bond or a single bond, R B represents a substituent, n2 represents an integer of 1 to 5, and * represents a bonding site with the rest of the above repeating unit, wherein at least one R B Represents hydroxyl.
[0035] [2] The resin composition according to [1], further comprising an additive, wherein the additive is contained in an amount of 50% by mass or less relative to the resin R.
[0036] [3] The resin composition according to [1] or [2], wherein the content of the repeating unit in the resin R is 2 mol% or more and 50 mol% or less relative to all the repeating units in the resin R.
[0037] [4] The resin composition according to any one of [1] to [3], wherein the repeating unit is any one of a repeating unit derived from a (meth)acrylate monomer, a repeating unit derived from a (meth)acrylamide monomer, and a repeating unit derived from an N-substituted maleimide monomer.
[0038] [5] The resin composition according to any one of [1] to [4], wherein the resin R further contains, in addition to the above-mentioned repeating units, a (meth)acrylate repeating unit having a linear or branched alkyl group having 1 to 5 carbon atoms in the side chain and / or a (meth)acrylate repeating unit having a hydroxyl group other than a phenolic hydroxyl group in the side chain.
[0039] [6] The resin composition according to any one of [1] to [4], wherein the resin R further contains an olefin-based repeating unit in addition to the repeating unit.
[0040] [7] The resin composition according to any one of [1] to [4], wherein the resin R further contains a halogen atom-containing repeating unit in addition to the repeating unit.
[0041] [8] A film comprising the resin composition according to any one of [1] to [7] above.
[0042] [9] The resin composition according to [1], which is an electron beam resist composition.
[0043]
[10] The resin composition according to [9], wherein the content of the repeating unit in the resin R is 2 mol% or more and 50 mol% or less relative to all the repeating units in the resin R.
[0044]
[11] The resin composition according to [9] or
[10] , wherein the repeating unit is any one of a repeating unit derived from a (meth)acrylate monomer, a repeating unit derived from a (meth)acrylamide monomer, and a repeating unit derived from an N-substituted maleimide monomer.
[0045]
[12] The resin composition according to [9], wherein the resin R further contains 2-hydroxyethyl methacrylate as a repeating unit.
[0046]
[13] A gas barrier laminate film comprising a resin substrate, a primer layer and a vapor-deposited film layer, wherein the primer layer and the vapor-deposited film layer are sequentially laminated on at least one surface of the resin substrate, wherein:
[0047] The primer layer is a layer derived from the resin composition according to [1], and contains a complex of a polyol and an isocyanate compound, and the resin R is the polyol.
[0048]
[14] The gas-barrier multilayer film according to
[13] , wherein the content of the repeating unit in the polyol is 2 mol% or more and 50 mol% or less relative to all the repeating units in the polyol.
[0049]
[15] The gas barrier multilayer film according to
[13] or
[14] , wherein the repeating unit is any one of a repeating unit derived from a (meth)acrylate monomer, a repeating unit derived from a (meth)acrylamide monomer, and a repeating unit derived from an N-substituted maleimide monomer.
[0050]
[16] The gas barrier multilayer film according to any one of
[13] to
[15] , wherein the primer layer further contains an organic additive.
[0051]
[17] A gas barrier laminate film according to any one of
[13] to
[16] , wherein a gas barrier coating layer is provided on the surface of the above-mentioned vapor-deposited film layer, and the gas barrier coating layer is a dry coating of a thin film formed by a coating liquid containing a water-soluble polymer and alkoxysilane or its hydrolysis product.
[0052]
[18] A packaging bag for heat sterilization, which is a packaging bag for heat sterilization formed by a laminated body in which a base film, a primer layer, a silicon oxide vapor-deposited layer, a gas barrier coating layer, and a heat-fusible adhesive layer are laminated in this order, wherein:
[0053] The primer layer is a layer derived from the resin composition according to [1], which contains a reaction product of acrylic polyol, isocyanate and silane coupling agent, and the resin R is the acrylic polyol.
[0054] The gas barrier coating layer is formed by a dried coating film of a coating liquid containing a silicon compound or its hydrolyzate or condensate and a water-soluble polymer having a hydroxyl group.
[0055] The silicon compound contains two of the following (a) and (b),
[0056] The mass of component (a) is converted into SiO2 and the mass of component (b) is converted into R 2 When Si(OH)3, R 2 The solid content of Si(OH)3 is 1 to 50% by mass relative to the total solid content, and the mass of component (a) is converted into SiO2, and the mass of component (b) is converted into R 2 When Si(OH)3 is used, the solid content ratio is SiO2 / (R 2 Si(OH)3+the above water-soluble polymer)=100 / 100 to 100 / 30,
[0057] (a) a silicon compound represented by the following general formula (III) or a hydrolyzate thereof,
[0058] Si(OR 1 )4 (III)
[0059] In the general formula (III), R 1 represents CH3, C2H5, or C2H4OCH3,
[0060] (b) a silicon compound represented by the general formula (IV), or a hydrolyzate or condensate thereof,
[0061] (R 2 Si(OR 3 )3)n (IV)
[0062] In the general formula (IV), R2 Represents an organic functional group, R 3 represents CH3, C2H5, or C2H4OCH3, and n represents 1 or more.
[0063]
[19] The thermal sterilization packaging bag according to
[18] , wherein the content of the repeating units having the partial structure represented by the general formula (I) or (II) in the acrylic polyol is 2 mol% or more and 50 mol% or less relative to all the repeating units of the acrylic polyol.
[0064]
[20] The thermal sterilization packaging bag according to
[18] or
[19] , wherein the repeating unit having the partial structure represented by the general formula (I) or (II) is any one of a repeating unit derived from a (meth)acrylate monomer, a repeating unit derived from a (meth)acrylamide monomer, and a repeating unit derived from an N-substituted maleimide monomer.
[0065]
[21] A packaging bag for heat sterilization according to any one of
[18] to
[20] , wherein the acrylic polyol further contains, in addition to the repeating unit having the partial structure represented by the general formula (I) or (II), a (meth)acrylate repeating unit having a linear or branched alkyl group having 1 to 5 carbon atoms in the side chain and / or a (meth)acrylate repeating unit having a hydroxyl group other than a phenolic hydroxyl group in the side chain.
[0066]
[22] The thermal sterilization packaging bag according to any one of
[18] to
[21] , wherein the acrylic polyol further contains an olefin-based repeating unit in addition to the repeating unit having the partial structure represented by the general formula (I) or (II).
[0067]
[23] The thermal sterilization packaging bag according to any one of
[18] to
[22] , wherein the acrylic polyol further contains a halogen-containing repeating unit in addition to the repeating unit having the partial structure represented by the general formula (I) or (II).
[0068]
[24] The thermal sterilization packaging bag according to any one of
[18] to
[23] , wherein the component (b) is a trimer 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate represented by the following general formula (V):
[0069] (NCO-R 4 Si(OR 3 )3)3 (V)
[0070] In the general formula (V), R 4 Represents (CH2)n, R 3represents CH3, C2H5, or C2H4OCH3, and n represents 1 or more.
[0071]
[25] The thermal sterilization packaging bag according to any one of
[18] to
[24] , wherein the gas barrier coating layer and the heat-fusible adhesive layer are bonded together using a dry lamination adhesive.
[0072]
[26] The thermal sterilization packaging bag according to any one of
[18] to
[25] , wherein a polyamide film is laminated between the gas barrier coating layer and the thermally fusible adhesive layer.
[0073]
[27] The thermal sterilization packaging bag according to any one of
[18] to
[26] , which has transparency.
[0074]
[28] A composition for forming a hard coat layer, wherein:
[0075] The resin composition according to [1] is a composition for forming a hard coat layer,
[0076] As raw materials, it contains:
[0077] A multifunctional (meth)acrylic monomer (A) selected from dipentaerythritol pentaacrylate hexamethylene diisocyanate urethane prepolymer, dipentaerythritol pentaacrylate toluene diisocyanate urethane prepolymer and dipentaerythritol pentaacrylate isophorone diisocyanate urethane prepolymer;
[0078] A monomer (B) having the above partial structure represented by the above general formula (I) or (II);
[0079] Photo radical polymerization initiator (C);
[0080] a fluorine-containing compound (D) having a polymerizable group; and
[0081] Non-polymerizable additives (E),
[0082] The content of the non-polymerizable additive (E) in the composition is 50% by mass or less.
[0083]
[29] A hard coat forming composition according to
[28] , wherein the content of the monomer (B) having the partial structure represented by the general formula (I) or (II) in the hard coat forming composition is 2 mol% or more and 50 mol% or less relative to the sum of the polyfunctional (meth)acrylic monomer and the fluorine-containing compound having a polymerizable group.
[0084]
[30] A hard coat forming composition according to
[28] or
[29] , wherein the monomer (B) having a partial structure represented by the general formula (I) or (II) is any one of a (meth)acrylate monomer, a (meth)acrylamide monomer, and an N-substituted maleimide monomer.
[0085]
[31] A hard coat forming composition according to any one of
[28] to
[30] , wherein the polyfunctional (meth)acrylic monomer (A) is contained in a ratio of 50% by mass or more and 95% by mass or less relative to the sum of the polyfunctional (meth)acrylic monomer (A) and the monomer (B) having the partial structure represented by the general formula (I) or (II).
[0086]
[32] A hard coating forming composition according to any one of
[28] to
[31] , wherein the amount of the fluorine-containing compound (D) having a polymerizable group added is 0.01% by mass or more and 10% by mass or less relative to the sum of the multifunctional (meth)acrylic monomer (A) and the monomer (B) having a partial structure represented by the general formula (I) or (II).
[0087]
[33] A hard coat forming composition according to any one of
[28] to
[32] , wherein the amount of the photoradical polymerization initiator (C) added is 0.01% by mass or more and 10% by mass or less relative to the sum of the polyfunctional (meth)acrylic monomer (A) and the monomer (B) having a partial structure represented by the general formula (I) or (II).
[0088]
[34] A hard coat film having a hard coat layer formed from a cured product of the hard coat layer forming composition according to any one of
[28] to
[33] on a transparent substrate, wherein the surface free energy of the hard coat layer surface is less than 20 mN / m and the film thickness of the hard coat layer is 5 to 25 μm.
[0089] Effects of the Invention
[0090] According to the present invention, it is possible to provide a resin composition that can suppress thermal degradation of additives and can be used in various applications, and a film comprising the resin composition. BRIEF DESCRIPTION OF THE DRAWINGS
[0091] Figure 1 This is a cross-sectional view schematically showing an example of a gas-barrier multilayer film according to one embodiment of the present invention.
[0092] Figure 2 This is a cross-sectional view schematically showing another example of the gas-barrier multilayer film according to one embodiment of the present invention.
[0093] Figure 3This is a cross-sectional view schematically showing an example of a gas barrier multilayer film having a double-sided lamination structure according to one embodiment of the present invention.
[0094] Figure 4 This is a cross-sectional view schematically showing an example of a packaging material constituting a heat sterilization packaging bag according to an embodiment of the present invention.
[0095] Figure 5 This is a cross-sectional view schematically showing another example of the packaging material constituting the heat sterilization packaging bag according to one embodiment of the present invention.
[0096] Figure 6 This is a cross-sectional view schematically showing an example of a hard coating film according to one embodiment of the present invention. DETAILED DESCRIPTION
[0097] Hereinafter, embodiments of the present invention will be described in detail.
[0098] <First Embodiment>
[0099] Hereinafter, a first embodiment of the present invention will be described.
[0100] The resin composition of the present embodiment contains a specific resin (hereinafter referred to as "resin R") with excellent heat resistance. When using a resin with low heat resistance such as a thermoplastic resin commonly used in daily necessities or industrial products, it is difficult to obtain a resin composition with excellent heat resistance and a desired function because it will promote the thermal degradation of the additives of the thermal decomposition products of the resin. The resin composition of the present embodiment described in detail below contains a resin R with excellent heat resistance, and since it will suppress the thermal degradation of the additives that can be used in combination, a film with excellent heat resistance and a desired function can be provided. Therefore, the resin composition of the present embodiment can be used in various applications.
[0101] <Resin R>
[0102] The resin R contained in the resin composition of the present embodiment contains a repeating unit (hereinafter referred to as "repeating unit (a)") having a partial structure represented by the following general formula (I) or (II).
[0103] [Chemical structure 3]
[0104]
[0105] In formula (I), Q A The ester bond shown in the formula, R A represents a substituent, n1 represents an integer of 1 to 5, * represents a bonding site to the remainder of the repeating unit (a), and ** represents a bonding site to the phenyl group in the formula.
[0106] As RA The substituent represented by may be, for example, an alkyl group (e.g., an alkyl group having 1 to 5 carbon atoms), a cycloalkyl group (e.g., a cycloalkyl group having 3 to 6 carbon atoms), an alkoxy group (e.g., a methoxy group or an ethoxy group), a hydroxyl group, an acetyl group, a nitro group, a cyano group, a carboxyl group, an amino group, an ester group, a halogen atom, etc. n1 represents an integer of 1 to 5 as described above, and may also be an integer of 1 to 3. When n1 is an integer of 2 or more, a plurality of R A Can be the same or different.
[0107] [Chemical structure 4]
[0108]
[0109] In formula (II), Q B represents the difference between Q in formula (I) A A linker other than an ester bond or a single bond, R B represents a substituent, n2 represents an integer of 1 to 5, and * represents a bonding site with the remainder of the repeating unit (a). B Represents hydroxyl.
[0110] Q B As mentioned above, it means that Q A A linker or single bond other than the ester bond shown as A Examples of linking groups other than the ester bond shown include -CONR- (R represents a hydrogen atom or an alkyl group), an alkylene group (for example, an alkylene group having 1 to 4 carbon atoms), a carbamate bond, an ether bond, an ester bond shown by *-O-CO-** (** represents a bonding site to the phenyl group in formula (II)), and the like.
[0111] As R B The substituent represented by may be, for example, an alkyl group (e.g., an alkyl group having 1 to 5 carbon atoms), a cycloalkyl group (e.g., a cycloalkyl group having 3 to 6 carbon atoms), an alkoxy group (e.g., a methoxy group, an ethoxy group), a hydroxyl group, an acetyl group, a nitro group, a cyano group, a carboxyl group, an amino group, an ester group, a halogen atom, etc. However, as mentioned above, at least one R B Represents hydroxyl.
[0112] n2 represents an integer of 1 to 5 as described above, or may be an integer of 1 to 3. When n2 is an integer of 2 or more, a plurality of R B Can be the same or different.
[0113] The repeating unit (a) may be any unit having a partial structure represented by the general formula (I) or (II) above, and may be, for example, a repeating unit derived from a (meth)acrylate monomer, a repeating unit derived from a (meth)acrylamide monomer, a repeating unit derived from an N-substituted maleimide monomer, or a repeating unit derived from a styrene monomer.
[0114] When the repeating unit (a) is a repeating unit derived from a (meth)acrylate monomer, examples of the (meth)acrylate monomer include 4-methoxyphenyl (meth)acrylate, 4-hydroxyphenyl (meth)acrylate, 2,6-di-tert-butylphenyl (meth)acrylate, 2,6-di-tert-butyl-4-methoxyphenyl (meth)acrylate, 2-tert-butyl-4-hydroxyphenyl (meth)acrylate, 3-tert-butyl-4-hydroxyphenyl (meth)acrylate, 2,6-di-tert-butyl-4-methylphenyl (meth)acrylate, 2-hydroxy-4-tert-butylphenyl (meth)acrylate, and 2,4-dimethyl-6-tert-butylphenyl (meth)acrylate.
[0115] When the repeating unit (a) is a repeating unit derived from a (meth)acrylamide-based monomer, examples of the (meth)acrylamide-based monomer include N-(4-hydroxyphenyl) (meth)acrylamide and the like.
[0116] When the repeating unit (a) is a repeating unit derived from an N-substituted maleimide monomer, examples of the N-substituted maleimide monomer include 4-hydroxyphenylmaleimide and 3-hydroxyphenylmaleimide.
[0117] When the repeating unit (a) is a repeating unit derived from a styrene-based monomer, examples of the styrene-based monomer include α-methyl-p-hydroxystyrene and the like.
[0118] In this embodiment, the resin R is preferably a copolymer of two or more members further containing one or more repeating units different from the repeating unit (a). In this case, the content of the repeating unit (a) in the resin R is preferably in the range of 2 mol% or more and 50 mol% or less relative to all the repeating units in the resin R. When the content of the repeating unit (a) in the resin is 2 mol% or more, when the resin R and the additive are contained, the thermal decomposition of the additive can be more effectively suppressed.
[0119] In addition, when the content of the repeating unit (a) in the resin R is 50 mol% or less, the effect of suppressing the thermal decomposition of the resin R and the additive used in combination can be maintained, and the yellowing of the resin R during heating, the hardening and brittleness of the resin R can be effectively suppressed. From the same viewpoint, the content of the repeating unit (a) in the resin R can be 2 mol% to 30 mol%, or 2 mol% to 20 mol%.
[0120] In the present embodiment, when the resin R is a copolymer, repeating units different from the repeating unit (a) (hereinafter referred to as "copolymer components") may be contained, for example, (meth)acrylate repeating units, olefin repeating units, halogen atom-containing repeating units, styrene repeating units, vinyl acetate repeating units, vinyl alcohol repeating units, etc.
[0121] Examples of the (meth)acrylate repeating unit as a copolymerization component include repeating units derived from a (meth)acrylate monomer having a linear or branched alkyl group in a side chain and repeating units derived from a (meth)acrylate monomer having a hydroxyl group (excluding a phenolic hydroxyl group) in a side chain.
[0122] Examples of the repeating unit derived from a (meth)acrylate monomer having a linear or branched alkyl group in the side chain include monomer-derived components such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, myristyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, and octadecyl (meth)acrylate. These may be used alone or in combination of two or more. Among the above, a (meth)acrylate-based repeating unit having a linear or branched alkyl group having 1 to 4 carbon atoms in a side chain may be preferably used.
[0123] Examples of the repeating unit derived from a (meth)acrylic acid monomer having a hydroxyl group other than a phenolic hydroxyl group in the side chain include monomer-derived components such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate. These may be used alone or in combination of two or more.
[0124] Examples of the olefin repeating unit as a copolymer component include components derived from olefin monomers such as ethylene, propylene, isobutylene, butadiene, etc. These may be used alone or in combination of two or more.
[0125] Examples of the halogen atom-containing repeating unit of the copolymerization component include monomer-derived components such as vinyl chloride and vinylidene chloride, which may be used alone or in combination of two or more.
[0126] Examples of the styrene-based repeating unit as a copolymerization component include components derived from styrene-based monomers such as styrene, α-methylstyrene, and vinyltoluene, and these may be used alone or in combination of two or more.
[0127] The copolymer can have any structure of a random copolymer, an alternating copolymer, a block copolymer and a graft copolymer. When the structure of the copolymer is a random copolymer, the manufacturing process and the blending with the cyanine pigment are easy. Therefore, random copolymers are more preferred than other copolymers.
[0128] The polymerization method for obtaining the copolymer can use free radical polymerization. Free radical polymerization is preferred in terms of easy industrial production. Free radical polymerization can be solution polymerization, emulsion polymerization, bulk polymerization, and suspension polymerization. Free radical polymerization preferably uses solution polymerization. By using solution polymerization, molecular weight control in the copolymer is easy.
[0129] In the radical polymerization, the monomers may be polymerized by diluting the monomers with a polymerization solvent and then adding a polymerization initiator.
[0130] The polymerization solvent may be, for example, an ester solvent, an alcohol ether solvent, a ketone solvent, an aromatic solvent, an amide solvent, and an alcohol solvent. Ester solvents may be, for example, methyl acetate, ethyl acetate, n-butyl acetate, isobutyl acetate, tert-butyl acetate, methyl lactate, and ethyl lactate. Alcohol ether solvents may be, for example, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether, 3-methoxy-1-butanol, and 3-methoxy-3-methyl-1-butanol. Ketone solvents may be, for example, acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone. Aromatic solvents may be, for example, benzene, toluene, and xylene. Amide solvents may be, for example, formamide and dimethylformamide. Alcohol solvents may be, for example, methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, tert-butanol, diacetone alcohol, and 2-methyl-2-butanol. Furthermore, among the above-mentioned polymerization solvents, one kind may be used alone, or two or more kinds may be mixed and used.
[0131] The amount of the polymerization solvent used in the radical polymerization is not particularly limited, but is preferably 1 to 1000 parts by mass, more preferably 10 to 500 parts by mass, based on 100 parts by mass of the total amount of the monomers.
[0132] The free radical polymerization initiator may be, for example, a peroxide and an azo compound. Peroxides may be, for example, benzoyl peroxide, tert-butyl peroxyacetate, tert-butyl peroxybenzoate, and di-tert-butyl peroxide. Azo compounds may be, for example, azobisisobutyronitrile, azobisamidinopropane salt, azobiscyanopivalic acid (salt), and 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], and the like.
[0133] The amount of the radical polymerization initiator used is preferably 0.0001 mass parts or more and 20 mass parts or less when the total amount of the monomer is set to 100 mass parts, more preferably 0.001 mass parts or more and 15 mass parts or less, and further preferably 0.005 mass parts or more and 10 mass parts or less. The radical polymerization initiator can be added before polymerization initiation relative to the monomer and the polymerization solvent, or it can be added dropwise to the polymerization reaction system. It is preferred that the radical polymerization initiator is added dropwise to the polymerization reaction system relative to the monomer and the polymerization solvent from the aspect of being able to suppress the heat release caused by polymerization.
[0134] The reaction temperature of the radical polymerization is appropriately selected according to the types of the radical polymerization initiator and the polymerization solvent. The reaction temperature is preferably 60° C. or higher and 110° C. or lower from the viewpoint of ease of production and reaction controllability.
[0135] <Additives>
[0136] The resin composition of the present embodiment achieves the thermal degradation inhibition effect of the additive by using a resin R with excellent heat resistance containing repeating units (a), so it is preferred to contain an additive. When the resin R contains an additive, the additive can be mixed with a mixing ratio of, for example, 50% by mass or less relative to the resin R. The mixing ratio of the additive to the resin R can be 30% by mass or less or can be 10% by mass or less. The lower limit of the mixing ratio of the additive can be appropriately set according to the purpose of use of the additive or the desired function, and is not particularly limited. When giving an example, the lower limit of the mixing ratio of the additive can be 0.01% by mass or more. The resin composition of the present embodiment can contain an additive alone, or it can contain two or more. When the resin composition of the present embodiment contains two or more additives, the mass ratio of the sum of the additives represented by the above mixing ratio relative to the resin R.
[0137] In this embodiment, the additive is added to the resin in the above-mentioned proportion for the purpose of maintaining the function of the resin R or imparting a new function, and is an organic additive. Here, the "organic additive" is an additive selected from compounds containing carbon atoms, and can be a low molecular weight compound, a high molecular weight compound, an oligomer, and can also include an organic metal salt.
[0138] However, the additive is a substance that is assumed not to chemically react with the resin R and exists in the composition with the same chemical structure after addition, and does not include a crosslinking agent or a curing agent that crosslinks resin chains with each other by heat or light.
[0139] Table 1 shows specific examples of the additives.
[0140] [Table 1-1]
[0141] Table 1
[0142]
[0143] [Table 1-2]
[0144] Table 1 (continued)
[0145]
[0146] The resin composition of the present embodiment can be preferably used as a coating film, a film substrate, an adhesive layer used when bonding film substrates to each other, and other thin film applications, among various applications requiring heat resistance. For example, gas barrier films in packaging materials such as food, medical supplies, and pharmaceuticals, optical films used in securities products with anti-counterfeiting structures, coating films (surface protection layers) used in building materials such as decorative boards, color filters or hard coating films used in liquid crystal displays, resist films for electron beam lithography, and the like can be cited.
[0147] <Second Embodiment>
[0148] Hereinafter, a second embodiment of the present invention will be described.
[0149] The resin composition of the present embodiment is an electron beam resist composition comprising a resin R containing a repeating unit (a) having a partial structure represented by the above general formula (I) or (II).
[0150] Electron beam lithography is essential in fields such as semiconductor manufacturing. The characteristics generally required of electron beam resists used in electron beam lithography are "high sensitivity", "high resolution" and "dry etching resistance". In order to improve these characteristics, various materials have been proposed. For example, as a representative example of positive electron beam resists, resists using polymethyl methacrylate (PMMA) have long been known as main chain cut-off type resists. Although they have high resolution, they have the disadvantages of low sensitivity and low production volume. Therefore, as a high-sensitivity positive electron beam resist, an example of using a copolymer resin having an aromatic ring in the side chain and suppressing the molecular weight distribution to less than 1.7 (Patent Document 1) as a main chain cut-off type resist is proposed; a two-component resist mixed with an alkali-soluble phenolic varnish resin and diazonaphthoquinone, a chemical amplification type resist using an acid catalytic reaction, etc. (Patent Document 2, Patent Document 3).
[0151] However, these compositions have insufficient dry etching resistance and are difficult to perform selective etching. According to the electron beam resist composition of the present embodiment described in detail below, an electron beam resist film having excellent dry etching resistance can be provided.
[0152] The electron beam resist composition of this embodiment can be suitable for both positive resist and negative resist. A positive resist is a resist in which the solubility of the exposed pattern in the developer increases, and the unexposed portion remains. A negative resist is a resist in which the solubility of the exposed pattern in the developer decreases after development, and the exposed portion remains after development.
[0153] The electron beam resist composition of the present embodiment includes a resin R containing a repeating unit (a) having a partial structure represented by the above general formula (I) or (II).
[0154] In this embodiment, the resin R is preferably a copolymer of two or more members further containing one or more repeating units different from the repeating unit (a). In this case, the content of the repeating unit (a) in the resin R is preferably in the range of 2 mol% or more and 50 mol% or less relative to all the repeating units in the resin R. When the content of the repeating unit (a) in the resin R is 2 mol% or more, the dry etching resistance can be further improved.
[0155] By using the resin as a copolymer having two or more valences, it is possible to impart a function of improving adhesion or to control the hardness of the resist film.
[0156] In addition, when the content of the repeating unit (a) in the resin R is 50 mol% or less, the inhibitory effect of the thermal decomposition of the resin R can be maintained, and the yellowing of the resist, the hardening and brittleness of the resist during heating can be effectively suppressed. From the same viewpoint, the content of the repeating unit (a) in the resin R can be 2 mol% to 30 mol%, or 2 mol% to 20 mol%.
[0157] In the present embodiment, when the resin R is a copolymer, examples of copolymer components that may be contained include (meth)acrylate repeating units, olefin repeating units, halogen atom-containing repeating units, styrene repeating units, vinyl acetate repeating units, and vinyl alcohol repeating units.
[0158] Examples of the (meth)acrylate repeating unit as a copolymerization component include repeating units derived from a (meth)acrylate monomer having a linear or branched alkyl group in a side chain and repeating units derived from a (meth)acrylate monomer having a hydroxyl group (excluding a phenolic hydroxyl group) in a side chain.
[0159] When using a resin as a positive resist, it is preferred to use a methacrylate repeating unit. By using a methacrylate repeating unit, only the position irradiated with the electron beam will selectively decompose the main chain, and it will become easy to dissolve during development. At this time, the content of the methacrylate repeating unit in the resin is preferably 30 mol% or more of all repeating units, and more preferably 50 mol% or more.
[0160] When using a resin as a negative resist, it is preferred to use an acrylate repeating unit. By using an acrylate repeating unit, only the position irradiated with the electron beam will be selectively cross-linked, and only the position not irradiated with the electron beam is easy to selectively dissolve during development. At this time, the content of the acrylate repeating unit in the resin is preferably 30 mol% or more of all repeating units, and more preferably 50 mol% or more.
[0161] Examples of the repeating unit derived from a (meth)acrylate monomer having a linear or branched alkyl group in a side chain include the same specific examples as those exemplified in the first embodiment.
[0162] Examples of the repeating unit derived from a (meth)acrylic monomer having a hydroxyl group other than a phenolic hydroxyl group in a side chain include the same specific examples as those exemplified in the first embodiment.
[0163] As a copolymerization component, 2-hydroxyethyl methacrylate can also be used. By using 2-hydroxyethyl methacrylate, the adhesion between the resist and the substrate can be improved.
[0164] As a copolymerization component, a monomer having a crosslinking functional group may be used. Examples of the monomer having a crosslinking functional group include glycidyl (meth)acrylate and the like. When such a component is used, it can be used as a negative resist.
[0165] Methacrylic acid can also be used as a copolymerization component. When methacrylic acid is used, the solubility in a developer during alkali development is improved, and the resolution of the pattern is improved.
[0166] Examples of the olefin-based repeating unit as a copolymerization component include the same specific examples as those exemplified in the first embodiment.
[0167] Examples of the halogen atom-containing repeating unit of the copolymerization component include the same specific examples as those exemplified in the first embodiment.
[0168] Examples of the styrene-based repeating unit as a copolymerization component include the same specific examples as those exemplified in the first embodiment.
[0169] The molecular weight of the resin R is not particularly specified, but specifically, the mass average molecular weight is 100,000 to 2,000,000, preferably 200,000 to 1,000,000. When the molecular weight is too large, there is no solvent with good solubility required for film coating, or gel is generated in the solution and cannot be filtered, and a uniform film cannot be obtained. In addition, when the molecular weight is too small, the sensitivity is reduced, and it is difficult to obtain a uniform film of appropriate thickness.
[0170] The copolymer may have any structure of a random copolymer, an alternating copolymer, a block copolymer, and a graft copolymer. If the structure of the copolymer is a random copolymer, the manufacturing process is easy. Therefore, a random copolymer is more preferred than other copolymers.
[0171] The polymerization method for obtaining the copolymer is as described in the first embodiment.
[0172] The resist composition of the present embodiment may contain additives such as a surfactant, a dissolution inhibitor, a plasticizer, a stabilizer, a colorant, and an antihalation agent for improving coating properties as appropriate.
[0173] In particular, in this embodiment, by using a resin R having excellent heat resistance containing repeating units (a), thermal degradation of an organic additive can be suppressed. Here, an "organic additive" is an additive selected from compounds containing carbon atoms, and may be a low molecular weight compound, a high molecular weight compound, an oligomer, or an organic metal salt. Specific examples of the additive are shown in Table 2.
[0174] [Table 2]
[0175]
[0176] As the solvent used when using the resist of this embodiment, for example, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, ethyl acetate, isobutyl acetate, methyl cellosolve acetate, ethyl cellosolve acetate, propylene glycol methyl ether acetate, ethyl lactate, toluene, xylene, 1,2-dichloroethane, etc. are used.
[0177] The resist pattern forming method of the present embodiment can be carried out as follows, for example. That is, first, the above-mentioned resist composition is coated on a substrate such as a silicon wafer or a glass substrate using a spinner, pre-baking is performed, and an electron beam is selectively irradiated thereon through a desired mask pattern using, for example, an electron beam drawing device. Then, a developer is used to develop the substrate. In this way, a resist pattern faithful to the mask pattern can be obtained. In addition, an organic or inorganic anti-reflection film can also be provided between the substrate and the coating layer of the resist composition.
[0178] The developer may be any developer as long as it can distinguish between the exposed portion and the unexposed portion and selectively dissolve the exposed portion or the unexposed portion. Generally, it is selected from the polymer mixture, that is, a combination of a soluble solvent and an insoluble solvent for the unexposed portion. As the soluble solvent, acetone, methyl ethyl ketone, methyl isobutyl ketone, methyl isoamyl ketone, cyclopentanone, cyclohexanone, 4-methoxy-4-methyl-2-pentanone, methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, isobutyl acetate, amyl acetate, methyl cellosolve acetate, ethyl cellosolve acetate, propyl cellosolve acetate, butyl cellosolve acetate, methyl carbitol acetate, ethyl carbitol acetate, propyl carbitol acetate, butyl carbitol acetate, 3-methyl-3-methoxybutyl acetate, propylene glycol mono Methyl ether acetate, butyl formate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, ethyl benzoate, ethyl-3-ethoxypropionate, methyl lactate, ethyl lactate, propyl lactate, butyl lactate, dimethyl cellosolve, diethyl cellosolve, tetrahydrofuran, methyl cellosolve, methyl carbitol, ethyl carbitol, propylene glycol monomethyl ether, diacetone alcohol, dimethylformamide, dimethylacetamide, dimethyl sulfoxide, nitromethane, nitroethane, 1-nitropropane, acetonitrile, toluene, xylene, chloroform, dichloromethane, etc. Examples of the insoluble solvent include methanol, ethanol, 1-propanol, isopropanol, 1-butanol, 2-butanol, cyclopentanol, cyclohexanol, ethyl cellosolve, propyl cellosolve, isopropyl cellosolve, butyl cellosolve, butyl carbitol, hexane, heptane, cyclohexane, petroleum ether, and water.
[0179] Next, generally, etching is performed using the resist pattern obtained as above as a mask to selectively remove the portion of the substrate not covered by the resist, etc. The resist composition of this embodiment can be preferably used because it has improved dry etching resistance in particular.
[0180] As a dry etching method, a known method can be used, such as chemical etching such as downflow etching or chemical dry etching; physical etching such as sputtering etching or ion beam etching; chemical-physical etching such as RIE (reactive ion etching) or the like.
[0181] <Third Embodiment>
[0182] Hereinafter, a third embodiment of the present invention will be described.
[0183] The present embodiment is a gas barrier multilayer film including a primer layer derived from the resin composition of the first embodiment.
[0184] Gas barrier laminate films protect objects from the effects of gases such as moisture, oxygen, and carbon dioxide in the air, and inhibit the deterioration of product quality and performance. Gas barrier laminate films are also being studied as a substitute for glass or aluminum foil in the electronics field such as solar cell backsheets, electronic paper, and organic EL, which are represented by packaging materials for food and medicine.
[0185] Currently, the main types of gas barrier laminated films include monomer films such as ethylene-vinyl alcohol copolymer resins, coextruded multilayer nylon (Ny) films, wet coating films coated with polyvinylidene chloride (PVDC) or polyvinyl alcohol (PVA), etc. However, even if these types of films have high gas barrier properties, their water vapor permeability is only 3g / m 2 / day, it is difficult to use it as a packaging material or electronic component that requires higher gas barrier properties. Therefore, when higher barrier properties are required, metal foil such as aluminum cannot be laminated.
[0186] However, packaging materials using a film laminated with a metal foil have problems such as the content being invisible and the inability to use a metal detector to inspect the content.
[0187] In order to overcome these problems, for example, Patent Document 4 proposes a transparent gas barrier film in which an inorganic compound such as aluminum oxide, magnesium oxide, or silicon oxide is deposited on a polymer resin substrate.
[0188] Furthermore, in order to improve the adhesion of the vapor-deposited layer on the resin substrate, many structures with a primer layer between the resin substrate and the vapor-deposited layer have been proposed. The materials of these primer layers are mostly acrylic resins, especially reaction complexes of acrylic polyols and isocyanate compounds or materials to which silane coupling agents are added. As a result, a gas barrier film with high boiling resistance, high temperature and high pressure resistance, and no deterioration of physical properties and no interlayer peeling after boiling sterilization or high temperature and high pressure sterilization is achieved (for example, patent documents 5 to 7).
[0189] However, these films have difficulty in maintaining adhesion even after a general high-temperature test (JIS C8917, C8938, C8990, C8991) as a durability test for solar cell modules, and thus have been difficult to use for applications requiring high durability.
[0190] Below, while referring to the attached Figure 1 The transparent gas barrier multilayer film of this embodiment which can maintain adhesion and excellent durability even after a high temperature test will be described in detail. Components having the same or similar functions are denoted by the same reference numerals, and repeated descriptions are omitted.
[0191] like Figure 1As shown, the gas barrier laminated film 10 of the present embodiment includes a resin substrate 11, a primer layer 12, and a vapor-deposited film layer 13, and is a structure in which the primer layer 12 and the vapor-deposited film layer 13 are sequentially laminated on one side of the resin substrate 11. In order to achieve higher water vapor barrier properties, the gas barrier laminated film may also be a structure in which the primer layer 12 and the vapor-deposited film layer 13 are sequentially laminated on both sides of the resin substrate 11.
[0192] As the resin substrate 11, for example, polyester films such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), polyolefin films such as polyethylene and polypropylene, polyethersulfone (PES), polystyrene films, polyamide films, polyvinyl chloride films, polycarbonate films, polyacrylonitrile films, polyimide films, biodegradable plastic films such as polylactic acid, etc. can be used. The thickness of the resin substrate 11 is not particularly limited, and can be practically about 6 μm or more and 200 μm or less, preferably 12 μm or more and 125 μm or less, and further preferably 12 μm or more and 25 μm or less.
[0193] Furthermore, the surface of the resin substrate 11 on which other layers are stacked may be subjected to physical treatment such as corona treatment, plasma treatment, or flame treatment, or chemical treatment such as acid or alkali liquid treatment to improve adhesion.
[0194] The primer layer 12 is provided on the resin substrate 11 to improve the adhesion between the resin substrate 11 and the vapor-deposited film layer 13 and to prevent the vapor-deposited layer from peeling off due to various sterilization treatments such as boiling sterilization or high-temperature and high-pressure sterilization or long-term placement outdoors.
[0195] The primer layer 12 comprises a composite of a polyol and an isocyanate compound. The primer layer 12 is a layer derived from the resin composition of the first embodiment, and in this case, the resin R containing the repeating unit (a) having the partial structure represented by the general formula (I) or (II) is a polyol.
[0196] Polyol is a general term for compounds having multiple hydroxyl groups in the molecule, and reacts with the isocyanate group of the isocyanate compound. Main polyols include polyether polyols having an ether bond in the main chain, polyester polyols having an ester bond in the main chain, acrylic polyols which are polymer compounds obtained by polymerizing (meth)acrylic acid derivative monomers, and acrylic polyols which are polymer compounds obtained by copolymerizing (meth)acrylic acid derivative monomers with other monomers.
[0197] Examples of the polyether polyol mainly include polyoxyalkylene polyols obtained by addition polymerization of alkylene oxides using polyols or polyamines as initiators, and polyoxytetramethylene glycols obtained by cationic polymerization of tetrahydrofuran.
[0198] Polyester polyols mainly include polycondensation polyester polyols obtained from dibasic acids and glycols, and polycaprolactone polyols obtained by ring-opening polymerization of ε-caprolactone. Dibasic acids used in polycondensation polyester polyols include adipic acid, terephthalic acid, isophthalic acid, and the like, and glycols include ethylene glycol, neopentyl glycol, and 3-methyl-1,5-pentanediol.
[0199] The acrylic polyol is a polymer compound obtained by polymerizing (meth)acrylic acid derivative monomers with each other, or a polymer compound obtained by copolymerizing a (meth)acrylic acid derivative monomer with other monomers by radical polymerization, and has a hydroxyl group at the terminal.
[0200] Examples of monomers copolymerizable with the (meth)acrylic acid derivative monomer having a hydroxyl group at the end include monomers having an alkyl group at the end, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, and tert-butyl (meth)acrylate; (meth)acrylic acid derivative monomers having a carboxyl group at the end, such as (meth)acrylic acid; and (meth)acrylic acid derivative monomers having an aromatic ring or a cyclic structure at the end, such as benzyl (meth)acrylate and cyclohexyl (meth)acrylate. In addition to the (meth)acrylic acid derivative monomer, there are styrene monomers, cyclohexylmaleimide monomers, phenylmaleimide monomers, and the like.
[0201] As described above, the polyol contains a repeating unit (a) having a partial structure represented by the above general formula (I) or (II).
[0202] In this embodiment, the polyol is preferably a copolymer of two or more valences or trivalences further containing one or more repeating units different from the repeating unit (a). In this case, the content of the repeating unit (a) in the polyol is preferably in the range of 2 mol% or more and 50 mol% or less relative to all the repeating units in the polyol. When the content of the repeating unit (a) in the polyol is 2 mol% or more, the thermal decomposition of the polyol can be more effectively suppressed.
[0203] In addition, when the content of the repeating unit (a) in the polyol is 50 mol% or less, the effect of suppressing the thermal decomposition of the polyol and the additive used in combination can be maintained, and the yellowing of the gas barrier film during heating and the hardening and brittleness of the primer layer 12 can be effectively suppressed. From the same viewpoint, the content of the repeating unit (a) in the resin can be 2 mol% to 30 mol%, or 2 mol% to 20 mol%.
[0204] In the present embodiment, examples of copolymer components that may be contained in the polyol as a copolymer include (meth)acrylate repeating units, olefin repeating units, halogen atom-containing repeating units, styrene repeating units, vinyl acetate repeating units, and vinyl alcohol repeating units.
[0205] Examples of the (meth)acrylate repeating unit as a copolymerization component include repeating units derived from a (meth)acrylate monomer having a linear or branched alkyl group in a side chain and repeating units derived from a (meth)acrylate monomer having a hydroxyl group (excluding a phenolic hydroxyl group) in a side chain.
[0206] Examples of the repeating unit derived from a (meth)acrylate monomer having a linear or branched alkyl group in a side chain include the same specific examples as those exemplified in the first embodiment.
[0207] As the (meth)acrylic repeating unit having a hydroxyl group other than a phenolic hydroxyl group in the side chain, the same specific examples as those listed in the first embodiment can be given.
[0208] Examples of the olefin-based repeating unit as a copolymerization component include the same specific examples as those exemplified in the first embodiment.
[0209] Examples of the halogen atom-containing repeating unit of the copolymerization component include the same specific examples as those exemplified in the first embodiment.
[0210] Examples of the styrene-based repeating unit as a copolymerization component include the same specific examples as those exemplified in the first embodiment.
[0211] However, when the repeating unit (a) does not contain a hydroxyl group, it is necessary to contain 2 mol % or more of a component having a hydroxyl group as a copolymerization component.
[0212] The molecular weight of the polyol is not particularly limited, but specifically, it may be 3,000 or more and 200,000 or less, preferably 5,000 or more and 100,000 or less, and more preferably 5,000 or more and 40,000 or less.
[0213] Copolymer can have any structure in random copolymer, alternating copolymer, block copolymer and graft copolymer.If the structure of copolymer is random copolymer, then manufacturing process and the deployment with cyanine pigment are easy.Therefore, random copolymer is more preferred than other copolymers.
[0214] The polymerization method for obtaining the copolymer is as described in the first embodiment.
[0215] Isocyanate compounds are compounds having two or more isocyanate groups in their molecules. For example, as monomeric isocyanates, there are aromatic isocyanates such as toluene diisocyanate (TDI) and diphenylmethane diisocyanate (MDI), aliphatic isocyanates such as hexamethylene diisocyanate (HDI), diisocyanate methylcyclohexane (H6XDI), isophorone diisocyanate (IPDI), dicyclohexylmethane diisocyanate (H12MDI), aromatic aliphatic isocyanates such as xylene diisocyanate (XDI) and tetramethylxylene diisocyanate (TMXDI), etc. In addition, polymers or derivatives of these monomeric isocyanates can also be used. For example, there are urate types of trimers to pentamers, adduct types formed by reaction with 1,1,1-trimethylolpropane, etc., and biuret types formed by reaction with biuret.
[0216] The isocyanate compound can be arbitrarily selected from the above-mentioned isocyanate compounds or polymers and derivatives thereof, and can be used alone or in combination of two or more.
[0217] In addition, in addition to the above-mentioned polyols and isocyanate compounds, additives can also be added according to the purpose. For example, there are catalysts that promote the curing reaction, light stabilizers such as ultraviolet light absorbers (UVA) or hindered amine light stabilizers (HALS), antioxidants, antistatic agents, plasticizers, silane coupling agents, etc. In particular, in the present embodiment, by using a polyol with excellent heat resistance containing repeating units (a), thermal degradation of organic additives can also be suppressed. Here, "organic additives" are as described in the second embodiment. As specific examples of additives, the same specific examples as those listed in Table 2 in the second embodiment can be cited.
[0218] By using a polyol containing the repeating unit (a), thermal degradation of additives can be suppressed. For example, when a light stabilizer is used as an additive, a gas barrier laminate film having excellent light resistance even after heating can be obtained.
[0219] The primer layer 12 is formed by coating a solution containing a complex of the polyol and the isocyanate compound and a solvent on the resin substrate 11 and allowing the solution to react and solidify. The solvent used can be any solvent that dissolves the polyol and the isocyanate compound, and examples thereof include methyl acetate, ethyl acetate, butyl acetate, methyl ethyl ketone, dioxolane, tetrahydrofuran, cyclohexanone, acetone, etc. These solvents can be used alone or in combination of two or more.
[0220] As a method for forming the primer layer 12, a common coating method can be used. For example, a known method such as dipping, roll coating, gravure coating, reverse coating, air knife coating, comma coating, die coating, screen printing, spray coating, gravure offset printing can be used. As a drying method, one of the methods of applying heat such as hot air drying, hot roll drying, high frequency irradiation, infrared irradiation, UV irradiation, etc. can be used, or two or more of them can be used in combination.
[0221] The film thickness of the primer layer 12 is preferably 30 nm to 200 nm, preferably 100 nm to 200 nm. When the thickness is thinner than this, the adhesion between the resin substrate 11 and the vapor-deposited film layer 13 becomes insufficient, and when the thickness is thicker than 300 nm, the influence of internal stress increases, the vapor-deposited film layer 13 cannot be perfectly laminated, and there is a problem that the barrier property becomes insufficient.
[0222] The vapor deposited film layer 13 is provided on the primer layer 12 and is provided to impart gas barrier properties to the entire film.
[0223] The material of the vapor-deposited film layer 13 is preferably a vapor-deposited material containing metal silicon and silicon dioxide. Alternatively, the material of the vapor-deposited film layer 13 may further contain other metal tin or metal oxide.
[0224] By vapor-depositing a vapor deposition material containing metal silicon and silicon dioxide, high gas barrier properties can be imparted to the entire film. Furthermore, by vapor-depositing a vapor deposition material in which metal tin or tin oxide is mixed with metal silicon and silicon dioxide, a vapor-deposited film layer 13 with high film density is formed, which exhibits high water vapor barrier properties, and a gas barrier film having both high gas barrier properties and high durability is obtained through a synergistic effect with the primer layer 12 formed of a composite of a polyol and an isocyanate compound.
[0225] Metal silicon and silicon dioxide may be mixed, for example, so that the element ratio O / Si is 1 to 1.8, preferably 1.2 to 1.7.
[0226] As a method for forming the vapor-deposited film layer 13, known methods such as vacuum vapor deposition, sputtering, plasma vapor deposition, and atomic layer deposition can be appropriately used, and vacuum vapor deposition is preferred. In addition, in order to improve the transparency of the vapor-deposited film layer 13, when the vapor deposition material is vapor-deposited, reactive vapor deposition can be performed by allowing the evaporated particles to react with oxygen or the like introduced into the ambient gas to be vapor-deposited. By performing reactive vapor deposition with oxygen or argon, the metal component in the vapor deposition material can be oxidized, thereby improving the transparency of the vapor-deposited film layer 13. When introducing the gas, it is preferred that the pressure in the film-forming chamber reaches 2×10 -1 Pa or less. When the pressure in the film forming chamber becomes greater than 2×10 -1When Pa is still too large, the vapor-deposited film layer 13 cannot be perfectly laminated, and the water vapor barrier property may be reduced.
[0227] The thickness of the deposited film layer 13 is preferably 0.005 μm to 0.3 μm, more preferably 0.03 μm to 0.05 μm. When the thickness is less than 0.005 μm, sufficient barrier properties may not be exhibited, while when the thickness exceeds 0.3 μm, the film becomes brittle and cracks easily, resulting in a lack of barrier properties.
[0228] The gas barrier multilayer film of this embodiment may also be Figure 2 As in the gas barrier laminated film 20 shown in FIG. 1 , a gas barrier coating layer 21 is provided on the vapor deposited film layer 13 as a dry coating of a thin film formed from a coating liquid containing a water-soluble polymer and alkoxysilane or a hydrolyzate thereof.
[0229] The gas barrier coating layer 21 is provided to protect the hard and brittle vapor-deposited film layer 13 and prevent cracks due to scratches or bending, and is formed of a component containing a water-soluble polymer and alkoxysilane or its hydrolyzate. The gas barrier coating layer 21 is formed by applying a coating liquid containing a water-soluble polymer and alkoxysilane or its hydrolyzate on the vapor-deposited film layer 13 and drying it.
[0230] As a method for forming the gas barrier coating layer 21, a common coating method can be used in the same manner as the primer layer 12. For example, known methods such as dipping, roll coating, gravure coating, reverse coating, air knife coating, comma coating, die coating, screen printing, spray coating, gravure offset printing, etc. can be used. As a drying method, one of the methods of applying heat such as hot air drying, hot roll drying, high frequency irradiation, infrared irradiation, UV irradiation, etc. can be used, or two or more of them can be used in combination.
[0231] As the water-soluble polymer, polyvinyl alcohol resin (PVA), ethylene-vinyl alcohol copolymer resin (EVOH), polyvinyl pyrrolidone resin (PVP) and the like can be used, and these can be used alone or in combination of two or more.
[0232] As the alkoxysilane, tetraethoxysilane, tetramethoxysilane, tetrapropoxysilane, methyltriethoxysilane, methyltrimethoxysilane, etc. can be used. In addition, as the hydrolyzate of alkoxysilane, there can be mentioned a substance prepared by dissolving alkoxysilane in an alcohol such as methanol and adding an aqueous solution of an acid such as hydrochloric acid to the solution to cause a hydrolysis reaction.
[0233] In order to improve the adhesion with the vapor-deposited film layer 13, a silane coupling agent may be added to the gas barrier coating layer 21. Examples of the silane coupling agent include those having an epoxy group such as 3-glycidyloxypropyltrimethoxysilane, those having an amino group such as 3-aminopropyltrimethoxysilane, those having a mercapto group such as 3-mercaptopropyltrimethoxysilane, and those having an isocyanate group such as 3-isocyanatepropyltriethoxysilane. One of these silane coupling agents may be used or two or more thereof may be used in combination.
[0234] The gas barrier multilayer film of this embodiment may also be Figure 3 As shown in the gas barrier laminate film 30, Figure 2 The gas barrier laminate film 20 shown has a structure in which a laminated resin layer is provided on both sides via an adhesive layer 31. By further providing a laminated resin layer 32, it becomes a gas barrier laminate film with high practicality. The laminated resin layer 32 is used in the adhesive portion when forming a bag-shaped package, etc. by laminating a sealant film having heat sealability. The laminated resin layer 32 uses resins such as polyethylene, polypropylene, ethylene-vinyl acetate copolymer, ethylene-methacrylic acid copolymer, ethylene-methacrylate copolymer, ethylene-acrylic acid copolymer, ethylene-acrylate copolymer and their metal cross-linked products. The thickness of the laminated resin layer 32 is determined according to the purpose, and is generally in the range of 15 μm to 200 μm. In addition, the laminated resin layer 32 can also be provided only on a single side of the gas barrier laminate film 20 via an adhesive layer 31.
[0235] In addition, by laminating a polyethylene terephthalate film or a polyethylene naphthalate film on one or both sides of the gas barrier laminate films 10, 20 and 30 of this embodiment, it can also be used as a sealing material such as a transparent conductive sheet used in liquid crystal display elements, solar cells, electromagnetic wave shielding devices, and touch panels.
[0236] <Fourth Embodiment>
[0237] Hereinafter, a fourth embodiment of the present invention will be described.
[0238] The present embodiment is a packaging bag for heat sterilization including a primer layer derived from the resin composition of the first embodiment.
[0239] In recent years, packaging materials used in the packaging of food, medicines, electronic components and other non-food products need to be protected from the effects of oxygen, water vapor and other gases that may deteriorate the contents that permeate through the packaging bag in order to suppress the deterioration of the contents and maintain the functions and properties of the contents. Therefore, they are required to have gas barrier properties that block these gases.
[0240] Conventionally, as a gas barrier layer, mainly used are resin films such as polyvinyl alcohol and ethylene vinyl copolymers, polyvinylidene chloride, and polyacrylonitrile, plastic films coated with these resins, or metal foils formed of metals such as aluminum or their metal vapor-deposited films.
[0241] In addition, as a gas barrier resin film, for example, a laminated film is known in which a coating layer is provided on a substrate formed of a resin by polycondensing a composition containing alkoxysilanes such as Si(O-CH3)4, silane coupling agents such as epoxysilane, and polyvinyl alcohol using a sol-gel method (see Patent Document 8). However, since the coating layer is formed by hydrogen bonds, it is easy to swell and dissolve due to water. Therefore, under harsh conditions such as boiling or high temperature and high pressure treatment, the gas barrier property is easily deteriorated.
[0242] On the other hand, metal foil or metal-deposited film has excellent gas barrier properties, but it is difficult to see through the packaging bag, the contents cannot be confirmed, metal detectors cannot be used during inspection, and they must be treated as non-combustibles when discarded. In addition, gas barrier resin films and films coated with gas barrier resins have a large temperature and humidity dependence and cannot maintain sufficient gas barrier properties. Furthermore, vinylidene chloride and polyacrylonitrile used as gas barrier resins may become raw materials of harmful substances when discarded or incinerated.
[0243] Thus, for example, Patent Document 9 proposes a gas barrier packaging material in which a vapor-deposited layer formed of an inorganic compound is used as a first layer, and a gas barrier coating layer formed by coating a solution containing a metal alkoxide or tin chloride and a water-soluble polymer and heating and drying is used as a second layer, which are sequentially stacked. The gas barrier packaging material exhibits high gas barrier properties, and has water resistance, moisture resistance, and a certain degree of heat resistance. However, since the second coating layer of the gas barrier packaging material is formed by hydrogen bonds between a metal alkoxide hydrolyzate and a water-soluble polymer having a hydroxyl group, when it is used as a packaging material that requires boiling and high-temperature and high-pressure sterilization, there are problems such as swelling of the coating layer and deterioration of the gas barrier properties such as water vapor barrier properties. For such packaging materials, such as disposable packaging bags for infusions, which require very high gas barrier properties, even slight deterioration cannot be used.
[0244] In addition, in the gas barrier packaging material in which an inorganic oxide vapor-deposited layer or a gas barrier coating layer is laminated on a substrate, if the adhesion is insufficient under harsh conditions such as boiling or high-temperature and high-pressure treatment, interlayer delamination may occur between the substrate and the inorganic oxide vapor-deposited layer, resulting in poor appearance, or the gas barrier properties are reduced in the part where the interlayer delamination occurs, or the contents are deteriorated.
[0245] The heat sterilization package of this embodiment solves the problems of the above-mentioned prior art, has excellent transparency, can see through the contents, and has high gas barrier properties (oxygen barrier properties and water vapor barrier properties). Furthermore, the heat sterilization package of this embodiment is not only suitable for metal detectors, but also can maintain high gas barrier properties (oxygen barrier properties and water vapor barrier properties) after heat sterilization treatments such as boiling and high temperature and high pressure sterilization, and is not prone to bag breakage or interlayer peeling.
[0246] Below, while referring to the attached Figure 1 The heat sterilization package body (hereinafter also referred to as "package body") of the present embodiment will be described. In addition, the same reference numerals are given to elements having the same or similar functions, and repeated descriptions are omitted.
[0247] The packaging bag of this embodiment is as follows Figure 4 As shown, the packaging material (laminate 100) may be composed of a base film 101, a primer layer 102, a silicon oxide vapor-deposited layer 103, a gas barrier coating layer 104, and a hot melt adhesive layer 105 laminated in sequence. The gas barrier coating layer 104 and the hot melt adhesive layer 105 may be bonded by an adhesive layer ad1 formed of an adhesive for dry lamination.
[0248] In addition, the packaging bag of this embodiment is as follows Figure 5 As shown, the packaging material (laminate 200) may be composed of a polyamide film 206 laminated between a gas barrier coating layer 104 and a heat-melting adhesive layer 105. The gas barrier coating layer 104 and the polyamide film 206, and the polyamide film 206 and the heat-melting adhesive layer 105 may be bonded by adhesive layers ad2 and ad3 formed of a dry lamination adhesive, respectively.
[0249] Next, the materials of the base film 101 and the layers 102 to 106 constituting the laminated body of the present embodiment will be described together with the method of forming each layer.
[0250] As the substrate film 101 used in the present embodiment, for example, polyester films such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyolefin films such as polyethylene or polypropylene, polystyrene films, polyamide films such as 6,6-nylon, polycarbonate films, polyacrylonitrile films, engineering plastic films such as polyimide films, etc. can be cited. The substrate film 101 can be either stretched or unstretched, and can have mechanical strength or dimensional stability. In particular, it is preferred to use a film that is stretched arbitrarily in a biaxial direction. Furthermore, when used in packaging materials, considering price, moisture resistance, filling suitability, feel and discardability, polyamide films and polyester films are preferred, and polyester films are more preferred. In addition, the substrate film 101 can also be a film to which various well-known additives or stabilizers, such as antistatic agents, plasticizers, lubricants, and antioxidants are added.
[0251] The thickness of the base film 101 is not particularly limited, but is preferably 3 to 200 μm, more preferably 6 to 30 μm, in practical terms, in consideration of suitability as a packaging material and processability.
[0252] In addition, in order to improve the adhesion, corona treatment, plasma treatment, ozone treatment, etc. may be performed as pretreatment on the surface of the substrate film 101. Furthermore, chemical reagent treatment and solvent treatment, etc. may also be performed on the surface of the substrate. In particular, plasma treatment is preferred because it makes the adhesion between the substrate surface and the primer layer 102 laminated thereafter firm.
[0253] Next, the primer layer 102 is described. The primer layer 102 is a layer derived from the resin composition of the first embodiment, and the primer layer 102 contains a reaction product of an acrylic polyol, an isocyanate, and a silane coupling agent. In this case, the resin R is an acrylic polyol, and contains a repeating unit (a) having a partial structure represented by the general formula (I) or (II).
[0254] In this embodiment, the acrylic polyol is preferably a copolymer of two or more members further containing one or more repeating units different from the repeating unit (a). In this case, the content of the repeating unit (a) in the acrylic polyol is preferably in the range of 2 mol% or more and 50 mol% or less relative to all the repeating units in the acrylic polyol. When the content of the repeating unit (a) in the acrylic polyol is 2 mol% or more, thermal degradation of the primer layer can be more effectively suppressed.
[0255] In addition, when the content of the repeating unit (a) in the acrylic polyol is 50 mol% or less, the inhibitory effect of thermal degradation of the primer layer can be maintained, and yellowing and cracking during heating can be suppressed. From the same viewpoint, the content of the repeating unit (a) in the acrylic polyol can be 2 mol% to 30 mol%, or 2 mol% to 20 mol%.
[0256] In the present embodiment, when the acrylic polyol is a copolymer, examples of copolymer components that may be contained include (meth)acrylate repeating units, olefin repeating units, halogen atom-containing repeating units, styrene repeating units, vinyl acetate repeating units, and vinyl alcohol repeating units.
[0257] Examples of the (meth)acrylate repeating unit as a copolymerization component include repeating units derived from a (meth)acrylate monomer having a linear or branched alkyl group in a side chain and repeating units derived from a (meth)acrylate monomer having a hydroxyl group (excluding a phenolic hydroxyl group) in a side chain.
[0258] Examples of the repeating unit derived from a (meth)acrylate monomer having a linear or branched alkyl group in a side chain include the same specific examples as those exemplified in the first embodiment.
[0259] As the (meth)acrylic repeating unit having a hydroxyl group other than a phenolic hydroxyl group in the side chain, the same specific examples as those listed in the first embodiment can be given.
[0260] Examples of the olefin-based repeating unit as a copolymerization component include the same specific examples as those exemplified in the first embodiment.
[0261] Examples of the halogen atom-containing repeating unit of the copolymerization component include the same specific examples as those exemplified in the first embodiment.
[0262] Examples of the styrene-based repeating unit as a copolymerization component include the same specific examples as those exemplified in the first embodiment.
[0263] The copolymer may have any structure of a random copolymer, an alternating copolymer, a block copolymer, and a graft copolymer. If the structure of the copolymer is a random copolymer, the manufacturing process is easy. Therefore, a random copolymer is more preferred than other copolymers.
[0264] The polymerization method for obtaining the copolymer is as described in the first embodiment.
[0265] Next, the isocyanate used in the primer layer 102 can be used as long as it has at least 2 NCO groups in the molecule. For example, as a monomeric isocyanate, aromatic isocyanates such as toluene diisocyanate (TDI) and diphenylmethane diisocyanate (MDI), aliphatic isocyanates such as hexamethylene diisocyanate (HDI), diisocyanate methylcyclohexane (H6XDI), isophorone diisocyanate (IPDI), dicyclohexylmethane diisocyanate (H12MDI), aromatic aliphatic isocyanates such as xylene diisocyanate (XDI), tetramethylbenzene diisocyanate (TMXDI), etc. can be used. In addition, polymers or derivatives of these monomeric isocyanates can also be used. As such polymers or derivatives, for example, urate type of trimer, adduct type formed by reaction with 1,1,1-trimethylolpropane, biuret type formed by reaction with biuret, etc. can be cited. The isocyanate compound can be arbitrarily selected from the above-mentioned monomeric isocyanates, polymers thereof, derivatives thereof, and the like, and can be used alone or in combination of two or more.
[0266] Next, examples of the silane coupling agent used in the primer layer 102 include those having an epoxy group such as 3-glycidoxypropyltrimethoxysilane, those having an amino group such as 3-aminopropyltrimethoxysilane, those having a mercapto group such as 3-mercaptopropyltrimethoxysilane, and those having an isocyanate group such as 3-isocyanatepropyltriethoxysilane. In addition, as the silane coupling agent, one type may be used alone, or two or more types may be used in combination.
[0267] The thickness of the primer layer 102 is generally measured as the thickness after drying, and is preferably applied in a range of 0.005 to 5 μm, more preferably 0.01 to 1 μm. When the thickness is less than 0.01 μm, it tends to be difficult to obtain a uniform coating film from the perspective of coating technology, and when it exceeds 1 μm, it tends to become uneconomical.
[0268] Next, the silicon oxide vapor-deposited layer 103 is described. The silicon oxide vapor-deposited layer 103 can be formed, for example, by vacuum vapor deposition. In order to improve the compactness or the adhesion to the primer layer 102, the vapor deposition can also be performed by a plasma-assisted method or an ion beam-assisted method. In addition, by using a reactive vapor deposition method in which the vapor deposition is performed while blowing in oxygen, the transparency of the formed silicon oxide vapor-deposited layer 103 can be further improved.
[0269] The thickness of the silicon oxide vapor-deposited layer 103 is preferably determined by considering both the gas barrier properties and its flexibility. When the thickness of the silicon oxide vapor-deposited layer 103 is too thin, it is difficult to fully function as a gas barrier layer. When the thickness of the silicon oxide vapor-deposited layer 103 is too thick, the flexibility cannot be maintained due to residual stress, and there is a risk of cracking due to external factors after film formation. The silicon oxide vapor-deposited layer 103 with a thickness in the range of 5 to 300 nm has sufficient gas barrier properties and flexibility. The thickness of the silicon oxide vapor-deposited layer 103 is preferably 10 to 300 nm.
[0270] Next, the gas barrier coating layer 104 is described. The gas barrier coating layer 104 is a coating layer formed as follows: the component (a) described below is used as the main component, a water-soluble polymer is added thereto, and then the component (b) described below is added to make a coating liquid, the coating liquid is applied to form a film, and the coating is heated and dried to hydrolyze the components (a) and (b) to form a coating layer. Here, the water-soluble polymer is added to the component (a) to improve the flexibility while maintaining its gas barrier properties. The component (b) is added to improve water resistance.
[0271] In order to control the hydrolysis of components (a) and (b), there is no problem even if a generally known catalyst, tin chloride or acetylacetonate is added. In addition, in consideration of the adhesion with ink and adhesive, wettability, and prevention of cracks due to shrinkage, isocyanate compounds, clay minerals such as colloidal silica or montmorillonite, or known additives such as stabilizers, colorants, and viscosity modifiers may be added to the coating liquid within a range that does not hinder gas barrier properties or water resistance.
[0272] (a) A silicon compound represented by the following general formula (III) or a hydrolyzate thereof.
[0273] Si(OR 1 )4(III)
[0274] In the general formula (III), R 1 It represents CH3, C2H5, or C2H4OCH3.
[0275] (b) A silicon compound represented by the general formula (IV), or a hydrolyzate or a condensate thereof.
[0276] (R 2 Si(OR 3 )3)n(IV)
[0277] In the general formula (IV), R 2 Represents an organic functional group, R 3 represents CH3, C2H5, or C2H4OCH3. In addition, n represents 1 or more.
[0278] The component (a) is a main component of the gas barrier coating layer 104 and is a compound represented by the above general formula (III). Examples thereof include tetramethoxysilane and tetraethoxysilane.
[0279] In addition, the water-soluble polymer is a substance used to improve the flexibility of the gas barrier coating layer 104 with component (a) as the main component while maintaining its gas barrier properties. For example, polyvinyl alcohol, starch, and cellulose can be preferably used. In particular, when polyvinyl alcohol (hereinafter referred to as PVA) is used in the coating agent of the present embodiment, the gas barrier properties are the best. The reason is that PVA is a polymer containing the most hydroxyl groups in the monomer unit, and therefore forms a very strong hydrogen bond with the hydroxyl group of the hydrolyzed metal alkoxide. The PVA mentioned here generally refers to a substance obtained by saponifying polyvinyl acetate, ranging from the so-called partially saponified PVA with tens of acetic acid groups remaining to the fully saponified PVA with only a few % of acetic acid groups remaining. The molecular weight of PVA is a degree of polymerization of 300 to several thousand, and there are many kinds, but no matter which molecular weight PVA is used, the effect is no problem. However, in general, high molecular weight PVA with a high degree of saponification and a high degree of polymerization has high water resistance, so it is preferred.
[0280] Next, the component (b) is a substance that improves the water resistance of the gas barrier coating layer 104 and is a silicon compound represented by the above-mentioned general formula (IV) or a hydrolyzate thereof.
[0281] As the component (b), organic functional groups R 2 Compounds having non-aqueous functional groups such as vinyl, epoxy, methacryloyl, urea, and isocyanate. Since the non-aqueous functional groups are hydrophobic, water resistance is further improved.
[0282] However, organic functional groups (R 2 ) is a urea group, the compound has a characteristic odor, while when it is an isocyanate group, it has the disadvantages of high reactivity and a short usable time.
[0283] In addition, a 3-glycidyloxypropyl group or a 2-(3,4-epoxycyclohexyl) group is used as the organic functional group R 2 When the compound is a compound, these organic functional groups react with Si(OR 1 )4 and water-soluble polymers form hydrogen bonds, so it is difficult to form pores in the barrier layer, and water resistance can be improved without damaging the gas barrier properties. However, some of these epoxy silane compounds are sometimes mutagenic. In addition, the organic functional group (R 2 ) is a vinyl group or a methacryloyl group, irradiation with ultraviolet rays or electron beams or the like is required in the production process, and there is a tendency for the cost to be high due to an increase in equipment and processes.
[0284] On the other hand, when 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate, a trimer represented by the following general formula (V), is used as the component (b), these disadvantages are eliminated, water resistance can be improved, and reduction in gas barrier properties can be prevented.
[0285] (NCO-R 4 Si(OR 3 )3)3(V)
[0286] (In the general formula (V), R 4 Represents (CH2)n, R 3 represents CH3, C2H5, or C2H4OCH3. In addition, n represents 1 or more).
[0287] That is, it is known that 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate is a condensate of 3-isocyanatepropylalkoxysilane. Through condensation, even if the isocyanurate portion has no chemical reactivity, due to the polarity of the urate portion, it also shows the same performance as the 3-isocyanatepropylalkoxysilane before condensation. Therefore, by adding 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate, the gas barrier coating layer 104 can be prevented from swelling due to water, just like adding 3-isocyanatepropylalkoxysilane, and water resistance can be improved. In addition, 3-isocyanatepropylalkoxysilane has high reactivity and low solution stability, and although the urate portion is non-water-soluble due to its polarity, it is easy to disperse in an aqueous solution, and the solution viscosity can be stably maintained, and its water resistance performance is equivalent to that of 3-isocyanatepropylalkoxysilane. Furthermore, the urate portion not only has water resistance, but also has polarity, Si(OR 1 )4 and water-soluble polymers having hydroxyl groups are not likely to form pores in the barrier layer, which can prevent the reduction of gas barrier properties.
[0288] In addition, 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate may be produced by thermal condensation of 3-isocyanatepropylalkoxysilane, or may contain 3-isocyanatepropylalkoxysilane as a raw material, but there is no particular problem. 1,3,5-tris(3-trimethoxysilylpropyl)isocyanuric acid is more preferred. Since the hydrolysis rate of the methoxy group is fast and the one containing the propyl group can be obtained at a relatively low price, 1,3,5-tris(3-trimethoxysilylpropyl)isocyanurate is practically advantageous.
[0289] Next, the mass of component (a) is converted into SiO2 and the mass of component (b) is converted into R 2 When Si(OH)3, R 2The solid content of Si(OH)3 is preferably 1 to 50% by mass relative to the total solid content (the sum of component (a) and component (b)). If it is within this range, the gas barrier coating layer 104 can obtain a gas barrier property with high water resistance and will not deteriorate even in harsh treatments such as boiling and high-temperature and high-pressure sterilization. When it is less than 1% by mass, there is a tendency for the water resistance effect to decrease. When it exceeds 50% by mass, the gas barrier property tends to decrease because the functional groups become pores in the gas barrier coating layer. In order to make the water resistance and high gas barrier property required for boiling, high-temperature and high-pressure sterilization treatment better, it is more preferred that the above-mentioned solid content is 5 to 30% by mass relative to the total solid content.
[0290] In addition, the mass of component (a) is converted into SiO2, and the mass of component (b) is converted into R 2 When Si(OH)3 is used, if the solid content ratio is SiO2 / (R 2 In the range of Si(OH)3+water-soluble polymer)=100 / 100 to 100 / 30, it can naturally fully impart the water resistance and high gas barrier properties required for boiling and high-temperature and high-pressure sterilization treatment, and can also fully impart the flexibility brought by the softness of the film when considered as a packaging material, which is preferred.
[0291] The mixing order of these three components can be arbitrary. The effect can be exhibited in any order. When component (a) or component (b) is not dispersed in the coating liquid but exists in the form of oil droplets, it is preferably hydrolyzed as described above to make it micro-dispersed. In particular, the micro-dispersion of SiO2 and Si(OR 1 )4, it is preferred that the components (a) and (b) are hydrolyzed separately and then added to the water-soluble polymer.
[0292] The thickness of the gas barrier coating layer 104 after drying is not particularly limited, but if the thickness exceeds 50 μm, cracks may be easily generated, so the thickness is preferably 0.01 to 50 μm.
[0293] As a method for forming the gas barrier coating layer 104, a common coating method can be used, for example, dipping, roll coating, gravure coating, reverse coating, air knife coating, comma coating, die coating, screen printing, spray coating, gravure offset printing, etc. can be used.
[0294] The coating film may be dried by any method as long as it is a method of applying heat to the gas barrier coating layer to disperse water molecules, such as hot air drying, hot roll drying, high frequency irradiation, infrared irradiation, UV irradiation, etc., and two or more of them may be combined. By this drying, the components (a) and (b) are hydrolyzed, and the gas barrier coating layer 104 having gas barrier properties can be formed.
[0295] Next, the thermally fusible adhesive layer 105 will be described. As the thermally fusible adhesive layer 105, for example, an unstretched polyolefin film can be used. The thickness thereof can be 5 to 300 μm, preferably 10 to 100 μm.
[0296] The hot melt adhesive layer 105 and the gas barrier coating layer 104 can be bonded by using a dry lamination adhesive ad1. The adhesive ad1 can be applied by a roll coating method, a gravure coating method, a knife coating method, a dip coating method, a spray coating method, or other coating methods. In addition, the coating amount is preferably 0.1 to 5.0 g / m 2 (Dry state) about.
[0297] Next, the polyamide film 206 is described. The polyamide film 206 can improve the pinhole resistance and impact resistance of the packaging bag, and for example, 6-nylon, 6,6-nylon, MXD nylon, etc. can be used. Preferably, the polyamide film is biaxially stretched, and its thickness can be 5 to 100 μm. Preferably, it is 10 to 50 μm. The polyamide film 206 and the gas barrier coating layer 104 can be bonded by the dry lamination adhesive layer ad2. In addition, the polyamide film 206 and the hot melt adhesive layer 105 can be bonded by the dry lamination adhesive ad3.
[0298] According to the present embodiment, a silicon compound is used as the metal alkoxide, and the silicon compound is reacted with a water-soluble polymer having a hydroxyl group, thereby making the gas barrier coating layer sufficiently insolubilized.
[0299] That is, the silicon compound condenses after hydrolysis to form a ceramic film. However, since silicon oxide is hard and is prone to cracking due to deformation caused by volume reduction during condensation, it is very difficult to form a thin, transparent, uniform condensate coating on the film. Therefore, by adding polymers, the ceramic film can be given flexibility, cracks can be prevented, and film can be formed. However, even if the addition of polymers is visually uniform, the metal oxide and polymer parts will separate microscopically and easily become pores in the barrier layer, so the gas barrier properties are reduced. In addition, here, the pores in the barrier layer refer to the parts in the film that do not form a dense network and make it easy for gas to pass through.
[0300] By using a water-soluble polymer having a hydroxyl group as the polymer, the strong hydrogen bond between the hydroxyl group of the polymer and the hydroxyl group of the hydrolyzate of the metal alkoxide is utilized, and the metal oxide is cleverly dispersed between the polymers during condensation, thereby maintaining flexibility while exhibiting high gas barrier properties close to those of ceramics.
[0301] However, in this case, since the gas barrier coating layer composed of the silicon compound and the water-soluble polymer is formed by hydrogen bonding, it swells and dissolves due to water.
[0302] Therefore, as a silicon compound, by reacting the above-mentioned component (a) with the component (b), the swelling of the gas barrier coating layer is prevented, and the water resistance is significantly improved. That is, the above-mentioned component (b) forms hydrogen bonds with the general formula (a) component and the water-soluble polymer through hydrolysis, so it is difficult to become a hole in the barrier layer. On the other hand, since the organic functional group forms a network, the water-soluble polymer is prevented from swelling due to the addition of water to its hydrogen bonds, and the water resistance is significantly improved. Therefore, the gas barrier coating layer 104 obtained by reacting the above-mentioned components (a) to (b) and the water-soluble polymer has excellent gas barrier properties and softness, and also has water resistance that can withstand heat sterilization treatments such as high temperature and high pressure or boiling.
[0303] In addition, on this basis, by providing the above-mentioned gas barrier coating layer on the substrate film in combination with the above-mentioned silicon oxide vapor-deposited layer, a higher gas barrier property is obtained. Furthermore, the package body of this embodiment has a primer layer containing an acrylic polyol containing a partial structure represented by general formula (I) or (II) between the substrate film and the silicon oxide vapor-deposited layer. Therefore, there is no deterioration in oxygen permeability and lamination strength after boiling sterilization and high temperature and high pressure sterilization, and the vapor-deposited layer is hardly peeled off from the substrate film.
[0304] <Fifth Embodiment>
[0305] Hereinafter, a fifth embodiment of the present invention will be described.
[0306] The resin composition of the present embodiment is a hard coat layer-forming composition comprising a resin R containing a repeating unit (a) having a partial structure represented by the general formula (I) or (II). Here, the repeating unit (a) is a repeating unit derived from a monomer (B) described later.
[0307] On the protective film of the circular polarizer used in the polarizer protective film for liquid crystal display or organic EL display, a resin layer is formed to give it various functions. The resin layer is, for example, an antistatic layer for giving it an antistatic function, an antireflection layer for suppressing reflection, and a hard coating layer for improving the surface hardness. In particular, it is necessary to provide a hard coating layer in display applications. The hard coating layer is not only used as a single layer, but also becomes the lower layer when the antireflection layer is stacked, and plays an important role.
[0308] As the application of these polarizers is widely expanded to LCD TVs, laptop computers, etc., various properties are required, including anti-reflection function with less reflection of fluorescent lights, anti-static function with difficulty in adhering dust, anti-fouling function of wiping fingerprints, etc. Especially in laptop computers, since people use them, there are many cases of dirt such as fingerprints, sebum, sweat, and cosmetics adhering. Generally speaking, the surface energy of polarizers is large, so such dirt is easy to adhere. In addition, since there are fine concave-convex on the surface of the anti-reflection film, it is difficult to remove the dirt. Furthermore, there is a problem that only the part with such dirt attached becomes highly reflective and the dirt becomes conspicuous.
[0309] Therefore, in order to solve these problems, various technologies have been proposed for forming an antifouling layer on the surface of an optical member, which has the property that dirt is difficult to adhere to and can be easily wiped off even if it adheres.
[0310] For example, Patent Document 10 proposes an anti-reflection article having an anti-reflection film mainly composed of silicon dioxide on the surface of a substrate and further treating the surface with a compound containing an organosilicon substituent. Patent Document 11 similarly proposes an anti-reflection CRT filter having an anti-reflection film having a substrate surface coated with a terminal silanol organopolysiloxane. In addition, Patent Document 12 proposes an anti-reflection plastic having an anti-reflection film containing a mono- and disilane compound containing a polyfluoroalkyl group and a halogen, alkyl or alkoxy silane compound on the surface.
[0311] In addition, various additives are generally mixed in the hard coat layer to improve the performance such as hot water resistance, weather resistance, scratch resistance, and wear resistance according to the application. In particular, when used in touch panel applications, various environmental resistance properties such as heat resistance or water absorption resistance are required. Therefore, for the additive, it is necessary to have heat resistance that can fully withstand the processing temperature or use temperature of the hard coat forming composition. In order to improve the heat resistance of the additive, for example, patent documents 13 to 15 disclose a technology for increasing the molecular weight of the additive.
[0312] However, the existing hard coating cannot take into account both antifouling properties such as fingerprint wiping properties and high heat resistance. In addition, additives mixed for the purpose of imparting functions to the hard coating will decompose to a certain extent at high temperatures, making it difficult to fully exert their functions. Furthermore, the thermal decomposition products of the additives often promote the degradation of the hard coating. Under such circumstances, in recent years, it has been expected to develop a hard coating forming composition that meets the high heat resistance requirements.
[0313] The present embodiment is completed in view of this technical problem. According to the hard coating composition of the present embodiment, a hard coating having excellent heat resistance, antifouling function, curling resistance, scratch resistance and surface hardness can be provided. In addition, the hard coating formed by the hard coating composition of the present embodiment has high adhesion to the substrate, simple removal of dirt, and no need to provide an antifouling layer. In addition, the characteristics of the hard coating will not deteriorate and the visibility is always high.
[0314] The present embodiment relates to a hard coating composition and a hard coating film used for the purpose of protecting the surface of displays such as cathode ray tube display devices (CRT), liquid crystal display devices (LCD), plasma display panels (PDP), field emission displays (FED), etc. More specifically, the present embodiment relates to a hard coating composition and a hard coating film that have high adhesion to a substrate, excellent heat resistance and antifouling properties, and can impart excellent curling resistance, scratch resistance, and surface hardness.
[0315] The present inventors have studied the imparting of antifouling properties to a hard coat layer on a transparent substrate and found that the above-mentioned prior art problems can be solved by using a hard coat layer forming composition comprising as raw materials a specific multifunctional (meth) acrylic monomer (A), a monomer (B) having a partial structure represented by the above general formula (I) or (II), a photoradical polymerization initiator (C), a fluorine-containing compound (D) having a polymerizable group, and a non-polymerizable additive (E). In the hard coat layer forming composition of the present embodiment, the proportion of the non-polymerizable additive (E) is adjusted to a specific range.
[0316] Below, while referring to the attached Figure 1 The hard coat layer-forming composition according to the present embodiment will be described in detail.
[0317] The multifunctional (meth) acrylic monomer (A) constituting the hard coat forming composition of the present embodiment is preferably a compound in which the hydroxyl groups of a polyol having two or more alcoholic hydroxyl groups in one molecule become esters of two or more (meth) acrylic acids. In addition, a substance having a reactive acrylic group bonded to an acrylic resin skeleton is used as a representative, and a substance having an acrylic group bonded to a rigid skeleton such as polyester acrylate, urethane acrylate, epoxy acrylate, polyether acrylate, and melamine or isocyanuric acid can also be used. In particular, when urethane (meth) acrylate monomers and / or oligomers are used, the hardness and flexibility of the hard coat can be significantly improved.
[0318] In addition, in the present embodiment, "(meth)acrylic monomer" means both "acrylic monomer" and "methacrylic monomer". For example, "multifunctional (meth)acrylic monomer" means both "multifunctional acrylic monomer" and "multifunctional methacrylic monomer". In addition, the multifunctional (meth)acrylic monomer (A) and the monomer (B) having a partial structure represented by general formula (I) or (II) in the present embodiment may also be an oligomer.
[0319] In the present embodiment, the carbamate acrylate preferably used as the multifunctional (meth) acrylic monomer (A) generally includes the carbamate acrylate easily formed by reacting an isocyanate monomer or a prepolymer with a polyester polyol, and reacting an acrylate monomer with a hydroxyl group. As a specific example, pentaerythritol triacrylate hexamethylene diisocyanate carbamate prepolymer, dipentaerythritol pentaacrylate hexamethylene diisocyanate carbamate prepolymer, pentaerythritol triacrylate toluene diisocyanate carbamate prepolymer, dipentaerythritol pentaacrylate toluene diisocyanate carbamate prepolymer, pentaerythritol triacrylate isophorone diisocyanate carbamate prepolymer, dipentaerythritol pentaacrylate isophorone diisocyanate carbamate prepolymer, etc. can be mentioned. In addition, these monomers can use one or more than two kinds in a mixed manner. In addition, they can be monomers or partially polymerized oligomers in the coating solution.
[0320] As commercially available multifunctional acrylic monomers, products of Mitsubishi Chemical Corporation [trade name, "Purple Light" series, etc.], Shin-Nakamura Chemical Co., Ltd. [trade name, "NK Ester" series, etc.], DIC Corporation [trade name, "Luxydir" series, etc.], Toagosei Co., Ltd. [trade name, "Aronix" series, etc.], NOF Corporation [trade name, "Blemmer" series, etc.], Nippon Kayaku Co., Ltd. [trade name, "KAYARAD" series, etc.], and Kyoeisha Chemical Co., Ltd. [trade name, "Light Ester" series, "Light Acrylate" series, etc.] can be used.
[0321] The hard coat layer-forming composition of the present embodiment contains a monomer (B) having a partial structure represented by the general formula (I) or (II). As described above, the repeating unit (a) is a repeating unit derived from the monomer (B).
[0322] The monomer (B) having a partial structure represented by the general formula (I) or (II) may be, for example, a (meth)acrylate monomer, a (meth)acrylamide monomer, an N-substituted maleimide monomer, or a styrene monomer.
[0323] When the monomer having a partial structure represented by the above general formula (I) or (II) is a (meth)acrylate monomer, examples thereof include 4-methoxyphenyl (meth)acrylate, 4-hydroxyphenyl (meth)acrylate, 2,6-di-tert-butylphenyl (meth)acrylate, 2,6-di-tert-butyl-4-methoxyphenyl (meth)acrylate, 2-tert-butyl-4-hydroxyphenyl (meth)acrylate, 3-tert-butyl-4-hydroxyphenyl (meth)acrylate, 2,6-di-tert-butyl-4-methylphenyl (meth)acrylate, 2-hydroxy-4-tert-butylphenyl (meth)acrylate, and 2,4-dimethyl-6-tert-butylphenyl (meth)acrylate.
[0324] When the monomer having a partial structure represented by the general formula (I) or (II) is a (meth)acrylamide-based monomer, examples thereof include N-(4-hydroxyphenyl) (meth)acrylamide and the like.
[0325] When the monomer having a partial structure represented by the general formula (I) or (II) is an N-substituted maleimide monomer, examples thereof include 4-hydroxyphenylmaleimide and 3-hydroxyphenylmaleimide.
[0326] When the monomer having a partial structure represented by the general formula (I) or (II) is a styrene-based monomer, examples thereof include α-methyl-p-hydroxystyrene and the like.
[0327] The proportion of the multifunctional (meth) acrylic monomer (A) used is preferably 1 to 99% by mass relative to the sum of the multifunctional (meth) acrylic monomer (A) and the monomer (B) having a partial structure represented by the general formula (I) or (II), and more preferably 50% by mass or more and 95% by mass or less. When the proportion of the multifunctional (meth) acrylic monomer (A) used is less than 50% by mass, it is sometimes insufficient in terms of obtaining a hard coating layer having sufficient hardness, and sometimes causes disadvantages such as a decrease in the pencil hardness of the formed hard coating layer. In addition, when the proportion of the multifunctional (meth) acrylic monomer (A) used exceeds 95% by mass, due to the curing shrinkage of the multifunctional (meth) acrylic monomer (A), it sometimes causes disadvantages such as severe curling of the hard coating film on the cured film side. In addition, since the proportion of the monomer (B) having a partial structure represented by the general formula (I) or (II) used is small, the compatibility of the fluorine-containing compound (D) having a polymerizable group is insufficient, which may cause the coating liquid to become turbid and generate precipitates, and is sometimes insufficient in terms of obtaining a hard coating composition with good storage stability.
[0328] As the photoradical polymerization initiator (C) constituting the hard coat layer forming composition of the present embodiment, a compound which generates radicals by irradiation with ionizing radiation and initiates a polymerization reaction of an acrylic monomer is preferred.
[0329] Specific examples of the photoradical polymerization initiator (C) include acetophenone, 2,2-diethoxyacetophenone, p-dimethylacetophenone, p-dimethylaminopropiophenone, benzophenone, 2-chlorobenzophenone, 4,4'-dichlorobenzophenone, 4,4'-bisdiethylaminobenzophenone, Michler's ketone, benzil, benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, p-isopropyl-α-hydroxyphenylisobutyl ketone, α-hydroxyphenylisobutyl ketone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexylphenyl ketone and other carbonyl compounds, tetramethylthiuram monosulfide, tetramethylthiuram disulfide, thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone and other sulfur compounds. These photopolymerization initiators may be used alone or in combination of two or more.
[0330] The amount of the photoradical polymerization initiator (C) used is preferably 0.01% by mass or more and 10% by mass or less relative to the sum of the multifunctional (meth)acrylic monomer (A) and the monomer (B) having a partial structure represented by the general formula (I) or (II) in the hard coat layer forming composition. When it is less than 0.01% by mass, sufficient curing reaction will not proceed when irradiated with ionizing radiation, and when it exceeds 10% by mass, the ionizing radiation will not sufficiently reach the lower part of the hard coat layer.
[0331] The fluorine-containing compound (D) with a polymerizable group constituting the hard coat forming composition of the present embodiment can impart antifouling properties to the hard coat surface by adding a fluorine-based additive. Here, when a fluorine-based additive is added to a fluorine-based compound without a polymerizable group, since the additive is in a state of floating on the hard coat surface and existing, it will be removed from the hard coat surface when wiping with a cloth or the like. Therefore, there is a disadvantage that the antifouling property disappears once the surface is wiped with a cloth or the like. In the present invention, by making the fluorine-based compound with antifouling properties have a polymerizable group, when the hard coat is formed, the fluorine-based additive is also polymerized, so there is an advantage that the antifouling property can be maintained even when the surface is wiped with a cloth or the like.
[0332] It is further preferred that the polymerizable group of the fluorinated compound (D) having a polymerizable group is a compound having a (meth)acrylate group. This is because the fluorinated compound (D) having a polymerizable group can also be copolymerized with a multifunctional (meth)acrylate compound, and high hardness can be achieved by free radical polymerization using ionizing radiation.
[0333] Examples of the fluorine-containing compound (D) having a polymerizable group according to the present embodiment include Optool DAC (manufactured by Daikin Industries, Ltd.), Defensa TF3001, Defensa TF3000, and Defensa TF3028 (manufactured by DIC Corporation).
[0334] The amount of the fluorinated compound (D) having a polymerizable group used in the present embodiment is appropriately 0.01 to 10% by mass relative to the sum of the multifunctional (meth) acrylic monomer (A) of the hard coat-forming composition and the monomer (B) having a partial structure shown in the general formula (I) or (II). When it is less than 0.01% by mass, sufficient antifouling properties will not be exhibited, and the surface energy also shows a value greater than 20mN / m. When it exceeds 10% by mass, due to poor compatibility with polymerizable monomers and solvents, it sometimes causes turbidity and precipitation of the coating liquid, resulting in defects in the coating liquid or the hard coat.
[0335] In this embodiment, the content of the monomer (B) having a partial structure represented by the general formula (I) or (II) is preferably in the range of 2 mol% or more and 50 mol% or less relative to the sum of the (meth)acrylic monomer (A) and the fluorinated compound (D) having a polymerizable group. When the content of the monomer (B) having a partial structure represented by the general formula (I) or (II) is 2 mol% or more, thermal decomposition of the hard coating film and the additive used in combination can be more effectively suppressed.
[0336] In addition, when the content of the monomer (B) having a partial structure represented by the general formula (I) or (II) is 50 mol% or less, the inhibitory effect on the thermal decomposition of the resin and the additive used in combination can be maintained, and the yellowing of the resin, the hardening of the resin, and the brittleness of the resin during heating can be effectively suppressed. From the same viewpoint, the content of the monomer (B) having a partial structure represented by the general formula (I) or (II) can be 2 mol% or more and 30 mol% or less, or can be 2 mol% or more and 20 mol% or less.
[0337] In addition, in the present embodiment, as a modifier for the hard coat, non-polymerizable additives (E) such as a coating improver, a defoamer, a thickener, an antistatic agent, an inorganic particle, an organic particle, an organic lubricant, an organic polymer compound, an ultraviolet absorber, a light stabilizer, a dye, a pigment or a stabilizer can be further added. These additives are used as the composition components of the coating layer constituting the hard coat within the range of the reaction performed by the active rays, and the characteristics of the hard coat can be improved according to the purpose. The proportion of the non-polymerizable additive (E) is less than 50% by mass of the mass sum of the components other than the solvent of the hard coat forming composition. As a specific example of the non-polymerizable additive (E), the specific examples identical to the specific examples listed in Table 1 in the first embodiment can be cited.
[0338] As the method for curing the hard coat forming composition of the present embodiment, preferably irradiating active rays, particularly irradiating ultraviolet rays, it is also possible to solidify it by adding a light free radical polymerization initiator and irradiating ultraviolet rays in the hard coat forming composition. In ultraviolet irradiation, as long as it is light comprising a wavelength below 400nm, for example, ultra-high pressure mercury lamps, high pressure mercury lamps, medium pressure mercury lamps, low pressure mercury lamps, xenon lamps, halogen lamps, etc. can be used. In addition, heating steps can also be added as required.
[0339] In the hard coat forming composition of the present embodiment, in order to prevent thermal polymerization during production or dark reaction during storage, a thermal polymerization inhibitor such as hydroquinone, hydroquinone monomethyl ether or 2,5-tert-butylhydroquinone is preferably added. The amount of the thermal polymerization inhibitor added is preferably 0.005 to 0.05 mass % relative to the solid content of the hard coat forming composition.
[0340] Figure 6 FIG. 1 is a cross-sectional view of a hard coating film according to an embodiment of the present invention. Figure 6 As shown, the hard coating film 300 of the present embodiment includes a hard coating layer 302 on a transparent substrate 301. The hard coating layer 302 is formed by applying the hard coating layer-forming composition of the present embodiment on the transparent substrate 301.
[0341] As a coating method for the hard coat forming composition, known coating means such as a rod coater, a dispenser, a scraper, a roll coater, a die coater, and a comma coater can be used. At this time, a solvent is also added to the hard coat forming composition as needed. As a solvent, methyl isobutyl ketone, cyclohexanone, acetone, methyl ethyl ketone, diethyl ketone, dipropyl ketone, cyclopentanone, methyl cyclohexanone, ethyl cyclohexanone, 2-butanone, ethyl formate, propyl formate, n-pentyl formate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, n-pentyl acetate, and γ-butyrolactone, isobutyl acetate, butyl acetate, toluene, xylene, 2-propanol, 1-butanol, cyclopentanol, diacetone alcohol can be used. , ethylene glycol monomethyl ether, propylene glycol monomethyl ether, dibutyl ether, dimethoxymethane, dimethoxyethane, diethoxyethane, propylene oxide, dioxane, dioxolane, trioxane, tetrahydrofuran, anisole, phenethyl ether, methyl cellosolve, cellosolve, butyl cellosolve, cellosolve acetate, dichloromethane, chloroform, trichloroethylene, ethylene chloride, trichloroethane, tetrachloroethane, N,N-dimethylformamide, chloroform, etc. In addition, the solvent is not limited to one kind, and a plurality of solvents may be mixed as a mixed solvent.
[0342] As the transparent substrate 301, a film-like material having light transmittance is preferred, as long as it has appropriate transparency and mechanical strength as a substrate. For example, films such as polyethylene terephthalate (PET), triacetyl cellulose (TAC), diacetyl cellulose, acetyl cellulose butyrate, polyethylene naphthalate (PEN), cycloolefin polymer, polyimide, polyether sulfone (PES), polymethyl methacrylate (PMMA), and polycarbonate (PC) can be used. Among them, when a hard coating film is provided in front of a liquid crystal display, triacetyl cellulose (TAC) is preferably used because it has no optical anisotropy.
[0343] The hard coating film 300 of the present embodiment includes a hard coating layer 302 as the outermost layer. In this case, the hard coating film 300 of the present embodiment preferably has a surface energy of 20 mN / m or less on the surface of the hard coating layer 302 .
[0344] The surface free energy can be used as an evaluation method index of the antifouling property of the hard coating layer 302 surface. The presence and magnitude of the antifouling property of the hard coating layer surface can be inferred from the surface free energy. The surface free energy can be obtained from the contact angle of the hard coating layer surface using the extended Fowkes formula. The smaller the value, the better the antifouling property. The hard coating film 300 of this embodiment has a high antifouling property because the surface free energy is 20 mN / m or less.
[0345] In addition, in the hard coating film 300 of the present embodiment, the surface free energy of the hard coating surface is preferably 15 mN / m or more. The smaller the value of the surface free energy, the higher the antifouling properties of the hard coating film can be made. However, when the surface free energy of the hard coating surface is less than 15 mN / m, it is necessary to add a considerable amount of a fluorine-containing compound (D) having a polymerizable group. At this time, the hard coating film formed by the hard coating forming composition whitens and becomes whitish, so the resulting hard coating film is sometimes not suitable for being arranged on the surface of the display.
[0346] The thickness of the hard coating layer 302 obtained by coating is determined according to the required hardness, but the preferred thickness is 3 to 30 μm, and more preferably 5 to 25 μm. If the thickness is less than 3 μm, sufficient hardness cannot be obtained, and if it exceeds 30 μm, the transparent substrate will be greatly curled due to the curing shrinkage of the hard coating layer 302, and undesirable conditions such as breakage may occur in the subsequent process.
[0347] Functional layers may also be provided in the hard coating film 300 of the present embodiment as required. The functional layer is provided between the transparent substrate 301 and the hard coating layer 302, or on the surface of the transparent substrate on the side where the hard coating layer 302 is not provided. Examples of these functional layers include anti-reflection layers, antistatic agents, anti-glare layers, electromagnetic wave shielding layers, infrared absorption layers, ultraviolet absorption layers, color correction layers, and the like. In addition, these functional layers may be used as a single layer, or multiple layers with different functions may be used. The hard coating film having a hard coating layer formed on the transparent substrate 301 and the hard coating film further provided with these functional layers may be bonded to the surfaces of various displays such as liquid crystal displays, plasma displays, and CRT displays, and may provide a display having excellent scratch resistance and antifouling properties.
[0348] Example
[0349] 《First Implementation Mode》
[0350] <Synthesis of Resin (Group A)>
[0351] Synthesis Example 1: Synthesis of Resin P-1a
[0352] 80 parts by mass of cyclohexanone were prepared as a polymerization solvent. In addition, 85 parts by mass of methyl methacrylate (MMA) and 15 parts by mass of 4-methoxyphenyl methacrylate (MPhMA) were prepared as acrylic acid monomers. Furthermore, 0.22 parts by mass of benzoyl peroxide (BPO) was prepared as a polymerization initiator. They were placed in a reaction vessel provided with a stirring device and a reflux tube, and nitrogen was introduced into the reaction vessel while heating to 80°C, and stirring and refluxing were performed for 8 hours. Thus, a polymer solution of an acrylic acid copolymer formed by repeating units derived from MMA and repeating units derived from MPhMA was obtained. The obtained polymer solution was added dropwise to a large amount of methanol for reprecipitation purification, and dried under reduced pressure at room temperature for 24 hours to obtain the resin P-1a described later.
[0353] Synthesis of Resin P-2a
[0354] In Synthesis Example 1, a resin P-2a described below was obtained by the same method as in Synthesis Example 1 except that 4-hydroxyphenyl methacrylate (HPMA) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0355] Synthesis of Resin P-3a
[0356] Resin P-3a described below was obtained by the same method as in Synthesis Example 1 except that N-(4-hydroxyphenyl)methacrylamide (HPMAA) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0357] Synthesis of Resin P-4a
[0358] In Synthesis Example 1, a resin P-4a described below was obtained by the same method as in Synthesis Example 1 except that 4-hydroxymaleimide (HPhMI) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0359] Synthesis of Resin P-101a
[0360] For comparison, a resin P-101a described later was obtained by the same method as in Synthesis Example 1 except that 4-methoxyphenyl methacrylate (MPhMA) was not used.
[0361] Synthesis of Resin P-102a
[0362] For comparison, a resin P-102a described below was obtained by the same method as in Synthesis Example 1 except that phenyl methacrylate (PhMA) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0363] Synthesis of Resin P-103a
[0364] For comparison, a resin P-103a shown below was obtained by the same method as in Synthesis Example 1 except that styrene (St) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0365] [Chemical structure 5]
[0366]
[0367] <Evaluation>
[0368] (Evaluation 1) Evaluation of heat resistance of resin
[0369] For each resin synthesized above, the mass reduction rate (%) under atmospheric environment and nitrogen environment is determined by the following method. In the determination of the mass reduction rate (%), a differential thermogravimetric simultaneous determination device (STA7000, manufactured by Hitachi High-Tech Science Co., Ltd.) is used. The sample is heated at 250°C for 20 minutes under atmospheric environment or nitrogen environment, and the mass reduction (M=M0-M1) obtained by subtracting the mass after heating (M1) from the initial mass before heating (M0) is divided by the initial mass (M0) to obtain the mass reduction rate ([M / M0]×100) (%). The lower the mass reduction rate, the better the heat resistance.
[0370] The case where the mass reduction rate was less than 20% in both the atmospheric atmosphere and the nitrogen atmosphere was designated as "A", and the case where the mass reduction rate was 20% or more in one or both of the atmospheric atmosphere and the nitrogen atmosphere was designated as "B". The results are shown in Table 3.
[0371] (Evaluation 2) Evaluation of the ability of additives to suppress thermal degradation
[0372] A resin solution was prepared by dissolving 20 parts by mass of the obtained resin in 80 parts by mass of cyclohexanone. 0.1 parts by mass of a hindered amine light stabilizer (trade name: Tinuvin (registered trademark) 123, manufactured by BASF Japan Co., Ltd.) or a cyanine pigment having a structure represented by the following formula (1) with a counter anion of tris(pentafluoroethyl)trifluorophosphoric acid (FAP) was added to the obtained resin solution as an additive to obtain a resin solution. The above resin solution was applied to a glass substrate using a spin coater, and dried by heating on a hot plate set at 200° C. for 10 minutes to form a coating film with a thickness of 1 μm.
[0373] The glass substrate on which the coating film was formed was heated at 250° C. for 10 minutes, and the residual rate of the additive in the coating film was measured. 2 The glass substrate was cut into different sizes, immersed in 1.5 mL of acetone, and extracted in an ultrasonic washing machine for 60 minutes. The additives in the glass substrate extract were quantified using ultra-high performance liquid chromatography / mass spectrometry (UHPLC / MS) (ultra-high performance liquid chromatography / mass spectrometry (UHPLC / MS), 1260LC System / 6130B Single Quad MS System manufactured by Agilent). The additive residual rate ([V1 / V0]×100) (%) was calculated by dividing the amount of additive remaining after heating (V1) by the initial amount of additive before heating (V0). The higher the additive residual rate, the better the ability of the additive to inhibit thermal degradation.
[0374] The case where the additive residual rate of the resin composition to which the hindered amine light stabilizer is added and the resin composition to which the cyanine pigment is added is 90% or more in both measurements is designated as "A", and the case where the additive residual rate of one or both measurements is less than 90% is designated as "B". The results are shown in Table 3.
[0375] [Chemical structure 6]
[0376]
[0377] [Table 3]
[0378]
[0379] <Synthesis of Resin (Group b)>
[0380] Synthesis Example 2: Synthesis of Resin P-1b
[0381] An autoclave reactor with an internal volume of 300 mL was prepared, and 20 mL of a 50% by mass methanol solution of 4-methoxyphenyl methacrylate (MPhMA) and 1 g of tert-butyl hydroperoxide as a polymerization initiator were added and dissolved. After the interior of the reactor was degassed, ethylene gas was introduced into the reactor, and a copolymer was produced at a pressure of 100 bar and a polymerization temperature of 175° C. The obtained copolymer was dissolved in xylene and reprecipitated and purified using methanol to obtain a resin P-1b described later.
[0382] Synthesis of Resin P-2b
[0383] In Synthesis Example 2, a resin P-2b described below was obtained by the same method as in Synthesis Example 2 except that 4-hydroxyphenyl methacrylate (HPMA) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0384] Synthesis of Resin P-101b
[0385] For comparison, a resin P-101b described later was obtained by the same method as in Synthesis Example 2 except that 4-methoxyphenyl methacrylate (MPhMA) was not used.
[0386] Synthesis of Resin P-102b
[0387] For comparison, a resin P-102b shown below was obtained by the same method as in Synthesis Example 2 except that benzyl methacrylate (BzMA) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0388] [Chemical structure 7]
[0389]
[0390] (Evaluation 3) Evaluation of heat resistance of resin
[0391] The heat resistance of each of the resins synthesized above was evaluated by the same method as in the above Evaluation 1. Table 4 shows the results.
[0392] (Evaluation 4) Evaluation of the ability of additives to suppress thermal degradation
[0393] 1 g of each of the synthesized resins was mixed with 0.01 g of a hindered amine light stabilizer (trade name: Tinuvin 123, manufactured by BASF Japan Co., Ltd.) or a cyanine pigment having a structure represented by the above formula (1) and having tris(pentafluoroethyl)trifluorophosphate (FAP) as an anion as an additive. The obtained mixture of the resin and the additive was placed on a glass substrate, and the glass substrate was heated on a hot plate at 200° C. for 10 minutes. An aluminum block heated to 200° C. was placed on the molten mixture, pressed at a force of 20 kgf for 10 seconds, and then rapidly cooled to room temperature. The pressed flaky mixture was peeled off from the glass substrate, immersed in 1.5 mL of acetone, and extracted in an ultrasonic washing machine for 60 minutes. The additive in the glass substrate extract was quantified using ultra-high performance liquid chromatography / mass spectrometry (UHPLC / MS) (ultra-high performance liquid chromatograph / mass spectrometer (UHPLC / MS), 1260LC System / 6130BSingle Quad MS System manufactured by Agilent). The residual additive ratio ([V1 / V0]×100)(%) is calculated by dividing the residual additive ratio (V1 / V0) after heating by the initial additive ratio (V0) before heating. The higher the residual additive ratio, the better the ability of the additive to suppress thermal degradation.
[0394] The case where the additive residual rate in both the resin composition to which the hindered amine light stabilizer is added and the resin composition to which the cyanine pigment is added is 90% or more is designated as "A", and the case where the additive residual rate in one or both of the measurements is less than 90% is designated as "B". The results are shown in Table 4.
[0395] [Table 4]
[0396]
[0397] <Synthesis of Resin (Group C)>
[0398] Synthesis Example 3: Synthesis of Resin P-1c
[0399] Prepare an autoclave reactor with an internal volume of 300 mL, add 0.1 g of potassium persulfate, 1.0 g of sodium lauryl sulfate, 12 mL of a 10% aqueous solution of partially saponified polyvinyl alcohol (polymerization degree of 500, saponification degree of 98.6%), and 50 mL of water, and dissolve them. Add 25 g of vinyl chloride monomer and react it at 45°C for 7 hours to obtain an emulsion solution. Freeze-dry the emulsion solution, recover the polyvinyl chloride precipitate, wash it with warm water, and dry it under reduced pressure. Dissolve the obtained powder in tetrahydrofuran, and filter and remove the polyvinyl alcohol as an insoluble substance. Inject the tetrahydrofuran solution into a large amount of methanol, filter the precipitate, and obtain polyvinyl chloride (PVC).
[0400] 0.8 g of the obtained PVC was dissolved in 10 mL of cyclohexanone, 0.2 g of 4-hydroxyphenyl methacrylate (HPMA) and 0.02 g of benzoyl peroxide were added, and the mixture was reacted at 80° C. for 8 hours under a nitrogen atmosphere. The obtained reaction solution was poured into a large amount of methanol, and the precipitate was filtered to obtain a polyvinyl chloride-based graft copolymer P-1c containing the repeating unit described below.
[0401] Synthesis of Resin P-2c
[0402] In Synthesis Example 3, a polyvinyl chloride-based graft copolymer P-2c including the repeating unit described below was obtained by the same method as Synthesis Example 3 except that N-(4-hydroxyphenyl)methacrylamide (HPMAA) was used instead of 4-hydroxyphenyl methacrylate (HPMA).
[0403] Synthesis of Resin P-3c
[0404] In Synthesis Example 3, a polyvinyl chloride-based graft copolymer P-3c including the repeating unit described below was obtained by the same method as Synthesis Example 3 except that 4-methoxyphenyl methacrylate was used instead of 4-hydroxyphenyl methacrylate (HPMA).
[0405] Synthesis of Resin P-101c
[0406] For comparison, a polyvinyl chloride-based graft copolymer P-101c including the repeating unit described below was obtained by the same method as in Synthesis Example 3 except that vinyl acetate (VAc) was used instead of 4-hydroxyphenyl methacrylate (HPMA).
[0407] Synthesis of Resin P-102c
[0408] For comparison, a polyvinyl chloride-based graft copolymer P-102c including the following repeating units was obtained by the same method as in Synthesis Example 3 except that methyl methacrylate (MMA) was used instead of 4-hydroxyphenyl methacrylate (HPMA).
[0409] [Chemical structure 8]
[0410]
[0411] <Evaluation>
[0412] (Evaluation 5) Evaluation of heat resistance of resin
[0413] For each of the resins synthesized above, the mass reduction rate ([M / M0]×100) (%) was measured by the same method as in Evaluation 1 under an atmospheric air atmosphere and a nitrogen atmosphere.
[0414] The case where the mass reduction rate was less than 30% in both the atmospheric atmosphere and the nitrogen atmosphere was designated as "A", and the case where the mass reduction rate was 30% or more in one or both of the atmospheric atmosphere and the nitrogen atmosphere was designated as "B". The results are shown in Table 5.
[0415] (Evaluation 6) Evaluation of the ability of additives to suppress thermal degradation
[0416] 1 g of each polyvinyl chloride graft copolymer was dissolved in 10 g of a solution of toluene:cyclohexanone=7:3 (mass ratio) to prepare a polymer solution. 0.01 g of a hindered amine light stabilizer (trade name: Tinuvin 123, manufactured by BASF Japan Co., Ltd.) or a cyanine pigment having a structure represented by the above formula (1) and tris(pentafluoroethyl)trifluorophosphate (FAP) as an anion was mixed into the polymer solution as an additive to obtain a resin solution. The above resin solution was applied on a glass substrate using a spin coater, and dried by heating on a hot plate set at 200°C for 10 minutes to form a coating film with a thickness of 1 μm.
[0417] The glass substrate on which the coating film was formed was heated at 250° C. for 10 minutes, and the residual rate of the additive in the coating film was measured. 2 The glass substrate was cut into different sizes, immersed in 1.5 mL of acetone, and extracted in an ultrasonic washing machine for 60 minutes. The additives in the glass substrate extract were quantified using ultra-high performance liquid chromatography / mass spectrometry (UHPLC / MS) (ultra-high performance liquid chromatography / mass spectrometry (UHPLC / MS), 1260LC System / 6130B Single Quad MS System manufactured by Agilent). The additive residual rate ([V1 / V0]×100) (%) was calculated by dividing the amount of additive remaining after heating (V1) by the initial amount of additive before heating (V0). The higher the additive residual rate, the better the ability of the additive to inhibit thermal degradation.
[0418] The case where the additive residual rate in both the resin composition to which the hindered amine light stabilizer is added and the resin composition to which the cyanine pigment is added is 80% or more is designated as "A", and the case where the additive residual rate in one or both of the measurements is less than 80% is designated as "B". The results are shown in Table 5.
[0419] [Table 5]
[0420]
[0421] <Synthesis of Resin (Group d)>
[0422] Synthesis Example 4: Synthesis of Resin P-1d
[0423] 80 parts by mass of cyclohexanone were prepared as a polymerization solvent. In addition, 13 parts by mass of methyl methacrylate (MMA), 4 parts by mass of 2-hydroxyethyl methacrylate (HEMA), and 3 parts by mass of 4-hydroxyphenyl methacrylate (HPMA) were prepared as acrylic monomers. Furthermore, 0.22 parts by mass of benzoyl peroxide (BPO) was prepared as a polymerization initiator. They were placed in a reaction vessel provided with a stirring device and a reflux tube, and nitrogen was introduced into the reaction vessel while heating to 80° C., and stirring and refluxing were performed for 8 hours. Thus, a polymer solution of the resin (acrylic copolymer) P-1d described later, which was formed by repeating units derived from MMA, repeating units derived from HEMA, and repeating units derived from HPMA, was obtained.
[0424] Synthesis of Resin P-2d
[0425] In Synthesis Example 4, a polymer solution containing resin P-2d described later was obtained by the same method as Synthesis Example 4 except that N-(4-hydroxyphenyl)methacrylamide (HPMAA) was used instead of 4-hydroxyphenyl methacrylate (HPMA).
[0426] Synthesis of Resin P-3d
[0427] In Synthesis Example 4, a polymer solution containing a resin P-3d described later was obtained by the same method as in Synthesis Example 4 except that 4-hydroxyphenylmaleimide (4-HPhMI) was used instead of 4-hydroxyphenyl methacrylate (HPMA).
[0428] Synthesis of Resin P-4d
[0429] In Synthesis Example 4, a polymer solution containing a resin P-4d described later was obtained by the same method as in Synthesis Example 4 except that 3-hydroxyphenylmaleimide (3-HPhMI) was used instead of 4-hydroxyphenyl methacrylate (HPMA).
[0430] Synthesis of Resin P-5d
[0431] In Synthesis Example 4, a polymer solution containing a resin P-5d described later was obtained by the same method as in Synthesis Example 4 except that 4-methoxyphenyl methacrylate (MPhMA) was used instead of 4-hydroxyphenyl methacrylate (HPMA).
[0432] Synthesis of Resin P-6d
[0433] In Synthesis Example 4, a polymer solution containing resin P-6d described later was obtained by the same method as Synthesis Example 4 except that 2,6-di-tert-butylphenyl methacrylate (t-BuPhMA) was used instead of 4-hydroxyphenyl methacrylate (HPMA).
[0434] Synthesis of Resin P-7d
[0435] In Synthesis Example 4, a polymer solution containing resin P-7d described later was obtained by the same method as Synthesis Example 4 except that 2,6-di-tert-butyl-4-methoxyphenyl methacrylate (t-BuMPhMA) was used instead of 4-hydroxyphenyl methacrylate (HPMA).
[0436] Synthesis of Resin P-101d
[0437] For comparison, a polymer solution containing resin P-101d described later was obtained by the same method as in Synthesis Example 4 except that phenyl methacrylate (PhMA) was used instead of 4-hydroxyphenyl methacrylate (HPMA).
[0438] Synthesis of Resin P-102d
[0439] For comparison, a polymer solution containing resin P-102d described later was obtained by the same method as in Synthesis Example 4 except that N-phenylmethacrylamide (PhMAA) was used instead of 4-hydroxyphenyl methacrylate (HPMA).
[0440] Synthesis of Resin P-103d
[0441] For comparison, a polymer solution containing the resin P-103d shown below was obtained by the same method as in Synthesis Example 4 except that N-phenylmaleimide (PhMI) was used instead of 4-hydroxyphenyl methacrylate (HPMA).
[0442] [Chemical structure 9]
[0443]
[0444] <Production of decorative panels>
[0445] A resin composition was obtained by adding 0.5 parts by mass of Tinuvin 326 (manufactured by BASF Japan Co., Ltd.) as an ultraviolet absorber, 0.4 parts by mass of Tinuvin 622 (manufactured by BASF Japan Co., Ltd.) as a light stabilizer, and 0.1 parts by mass of Chimassorb 2020 (manufactured by BASF Japan Co., Ltd.) to 100 parts by mass of a transparent homopolypropylene resin (Prime PP; manufactured by Prime Polymer Co., Ltd.). The resin composition was melt-extruded to obtain a polypropylene resin film having a thickness of 80 μm.
[0446] A wood grain pattern was gravure-printed on a polyethylene blank (70 μm thick) with a hidden property using a two-component urethane ink (V180; manufactured by Toyo INK Co., Ltd.) to provide a pattern layer (3 μm thick) to obtain a substrate. The polypropylene resin film was dry-laminated on the substrate via a dry lamination adhesive (Takelac A540; manufactured by Mitsui Chemicals, Inc.) (2 μm thick) to obtain a laminate of films.
[0447] On the polypropylene resin film of the above-mentioned laminate, the polymer solution containing each resin (acrylic copolymer) obtained above is applied to the polypropylene resin film in a manner of 8 μm in thickness using a rod coater and dried to form a surface protective layer, thereby obtaining a decorative sheet. Here, as the polymer solution for the surface protective layer, 4 polymer solutions are prepared for each resin. That is, 4 solutions are prepared for the polymer solution containing the above-mentioned resin itself, a polymer solution obtained by adding xylylene diisocyanate (XDI) (trade name: Takenate (registered trademark) 500; manufactured by Mitsui Chemicals, Inc.) as a curing agent in a manner of 7:3 in terms of solid content mass ratio of resin: curing agent, and a hindered amine-based light stabilizer (trade name: Tinuvin 123; manufactured by BASF Japan Co., Ltd.) as an additive.
[0448] <Evaluation>
[0449] (Evaluation 7) Evaluation of heat resistance of surface protective layer
[0450] The mass reduction rate (%) of the surface protective layer under atmospheric environment gas is determined by the following method. The mass reduction rate (%) is determined using a differential thermal thermogravimetric simultaneous measuring device (STA7000, manufactured by Hitachi High-TechScience Co., Ltd.). 5 mg of the surface protective layer is shaved off from the decorative plate obtained above, and the plate is placed in an aluminum pan to prepare a measurement sample. The sample is heated at 250°C for 20 minutes under atmospheric environment gas, and the mass reduction amount (M=M0-M1) obtained by subtracting the mass after heating (M1) from the initial mass before heating (M0) is divided by the initial mass (M0) to calculate the mass reduction rate ([M / M0]×100) (%). The lower the mass reduction rate, the better the heat resistance.
[0451] The case where the mass reduction rate was less than 20% was designated as "A", and the case where it was 20% or more was designated as "B".
[0452] (Evaluation 8) Evaluation of the ability of additives to suppress thermal degradation
[0453] Cut the decorative board obtained above into 1cm 2 The sample was prepared by heating at 250°C for 20 minutes under atmospheric environment, immersed in 1.5 mL of acetone, and extracted in an ultrasonic washing machine for 60 minutes. The additives in the decorative sheet extract were quantified by ultra-high performance liquid chromatography / mass spectrometry (UHPLC / MS) (Ultra-high performance liquid chromatography / mass spectrometry (UHPLC / MS), Agilent 1260LCSystem / 6130B Single Quad MS System).
[0454] Separately, the above-mentioned film laminate without a surface protective layer was prepared, and 1 cm thick pieces were cut out in the same manner as above. 2 The same heating treatment and extraction operation as above are carried out to quantify the additive in the extract of the membrane stack.
[0455] The amount of the additive in the surface protection layer of the decorative sheet is quantified by obtaining the difference between the amount of the additive in the extract of the decorative sheet and the amount of the additive in the extract of the film laminate.
[0456] The residual additive rate ([V1 / V0]×100)(%) was calculated by dividing the residual additive amount (V1) after heating by the initial additive amount (V0) before heating. The higher the residual additive rate, the better the ability of the additive to suppress thermal degradation. The case where the residual additive rate is 90% or more is designated as "A", and the case where it is less than 90% is designated as "B". The results are shown in Table 6.
[0457] [Table 6-1]
[0458] Table 6
[0459]
[0460] [Table 6-2]
[0461] Table 6 (continued)
[0462]
[0463] [Table 6-3]
[0464] Table 6 (continued)
[0465]
[0466] [Table 6-4]
[0467] Table 6 (continued)
[0468]
[0469] [Table 6-5]
[0470] Table 6 (continued)
[0471]
[0472] Second Implementation Method
[0473] <Synthesis of Resin>
[0474] 17 types of resins were synthesized and designated as Pa to Pq. The structural formula of the repeating unit contained in the resins Pa to Pq will be disclosed later. In addition, the synthesis method of each resin will be described below.
[0475] Synthesis Example 1: Synthesis of Resin Pa
[0476] 80 parts by mass of cyclohexanone were prepared as a polymerization solvent. In addition, 3 parts by mass of 2-hydroxyethyl methacrylate (HEMA), 14 parts by mass of methyl methacrylate (MMA), and 1 part by mass of 4-methoxyphenyl methacrylate (MPhMA) were prepared as acrylic acid monomers. Furthermore, 0.22 parts by mass of benzoyl peroxide (BPO) were prepared as a polymerization initiator. They were placed in a reaction vessel provided with a stirring device and a reflux tube, and nitrogen was introduced into the reaction vessel while heating to 80°C, and stirring and refluxing were performed for 8 hours. Thus, a polymer solution of an acrylic acid copolymer formed by repeating units derived from HEMA, repeating units derived from MMA, and repeating units derived from MPhMA was obtained. The obtained polymer solution was added dropwise to a large amount of methanol for reprecipitation purification, and dried under reduced pressure at room temperature for 24 hours to obtain resin Pa.
[0477] Synthesis Example 2: Synthesis of Resin Pb
[0478] Regarding Synthesis Example 1, a resin Pb was obtained by the same method as Synthesis Example 1 except that 4-hydroxyphenyl methacrylate (HPMA) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0479] Synthesis Example 3: Synthesis of Resin Pc
[0480] About Synthesis Example 2, the resin Pc was obtained by the same method as Synthesis Example 2 except having changed methyl methacrylate (MMA) into 16.6 parts by mass and 4-hydroxyphenyl methacrylate (HPMA) into 0.4 parts by mass.
[0481] Synthesis Example 4: Synthesis of Resin Pd
[0482] About Synthesis Example 2, resin Pd was obtained by the same method as Synthesis Example 2 except having changed methyl methacrylate (MMA) into 15 parts by mass and 4-hydroxyphenyl methacrylate (HPMA) into 2 parts by mass.
[0483] Synthesis Example 5: Synthesis of Resin Pe
[0484] Regarding Synthesis Example 1, a resin Pe was obtained by the same method as Synthesis Example 1 except that 4-hydroxyphenylmethacrylamide (HPMAA) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0485] Synthesis Example 6: Synthesis of Resin Pf
[0486] Regarding Synthesis Example 1, a resin Pf was obtained by the same method as Synthesis Example 1 except that 4-hydroxyphenylmaleimide (HPhMI) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0487] Synthesis Example 7: Synthesis of Resin Pg
[0488] Resin Pg was obtained by the same method as in Synthesis Example 1 except that 2,6-di-tert-butylphenyl methacrylate (t-BuPhMA) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0489] Synthesis Example 8: Synthesis of Resin Ph
[0490] Regarding Synthesis Example 1, a resin Ph was obtained by the same method as Synthesis Example 1 except that 2,6-di-tert-butyl-4-methoxyphenyl methacrylate (t-BuMPhMA) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0491] Synthesis Example 9: Synthesis of Resin Pi
[0492] Resin Pi was obtained by the same method as in Synthesis Example 1 except that 14 parts by mass of 4-hydroxyphenyl acrylate (HPA) and 6 parts by mass of glycidyl acrylate (GA) were used instead of 2-hydroxyethyl methacrylate (HEMA), methyl methacrylate (MMA) and 4-methoxyphenyl methacrylate (MPhMA).
[0493] Synthesis Example 10: Synthesis of Resin Pj
[0494] About Synthesis Example 1, resin Pj was obtained by the same method as Synthesis Example 1 except having used 17 parts by mass of methyl methacrylate (MMA) and not using 4-methoxyphenyl methacrylate (MPhMA).
[0495] Synthesis Example 11: Synthesis of Resin Pk
[0496] Regarding Synthesis Example 1, a resin Pk was obtained by the same method as Synthesis Example 1 except that styrene (St) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0497] Synthesis Example 12: Synthesis of Resin P1
[0498] Regarding Synthesis Example 1, a resin P1 was obtained by the same method as Synthesis Example 1 except that phenyl methacrylate (PhMA) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0499] Synthesis Example 13: Synthesis of Resin Pm
[0500] Regarding Synthesis Example 1, a resin Pm was obtained by the same method as Synthesis Example 1 except that phenylmethacrylamide (PhMAA) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0501] Synthesis Example 14: Synthesis of Resin Pn
[0502] Regarding Synthesis Example 1, a resin Pn was obtained by the same method as Synthesis Example 1 except that phenylmaleimide (PhMI) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0503] Synthesis Example 15: Synthesis of Resin Po
[0504] Regarding Synthesis Example 1, a resin Po was obtained by the same method as Synthesis Example 1 except that 4-methoxystyrene (MSt) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0505] Synthesis Example 16: Synthesis of Resin Pp
[0506] Regarding Synthesis Example 1, a resin Pp was obtained by the same method as Synthesis Example 1 except that 2,4,6-trimethylstyrene (TMSt) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0507] Synthesis Example 17: Synthesis of Resin Pq
[0508] Regarding Synthesis Example 9, a resin Pq was obtained by the same method as Synthesis Example 9 except that styrene (St) was used instead of 4-hydroxyphenyl acrylate (HPA).
[0509] [Chemical structural formula 10-1]
[0510]
[0511] [Chemical structure formula 10-2]
[0512]
[0513] <Formation of Resist Film>
[0514] The resist films of Examples 201 to 209 and Examples 201C to 208C were formed in the order of the following steps (1) to (4) and evaluated.
[0515] (1) Preparation step of resist solution (Example 201)
[0516] A 6 mass % propylene glycol monomethyl ether acetate (PGMEA) solution of the resin Pa was prepared, and the solution was filtered under pressure using a 0.1 μm Teflon (registered trademark) filter to prepare a positive resist solution.
[0517] (Example 202)
[0518] A positive resist solution was prepared in the same manner as in Example 201 except that a 6 mass % propylene glycol monomethyl ether acetate (PGMEA) solution of the resin Pb was used.
[0519] (Example 203)
[0520] A positive resist solution was prepared in the same manner as in Example 201 except that a 6 mass % propylene glycol monomethyl ether acetate (PGMEA) solution of the resin Pc was used.
[0521] (Example 204)
[0522] A positive resist solution was prepared in the same manner as in Example 201 except that a 6 mass % propylene glycol monomethyl ether acetate (PGMEA) solution of resin Pd was used.
[0523] (Example 205)
[0524] A positive resist solution was prepared in the same manner as in Example 201 except that a 6 mass % propylene glycol monomethyl ether acetate (PGMEA) solution of the resin Pe was used.
[0525] (Example 206)
[0526] A positive resist solution was prepared in the same manner as in Example 201 except that a 6 mass % propylene glycol monomethyl ether acetate (PGMEA) solution of the resin Pf was used.
[0527] (Example 207)
[0528] A positive resist solution was prepared in the same manner as in Example 201 except that a 6 mass % propylene glycol monomethyl ether acetate (PGMEA) solution of the resin Pg was used.
[0529] (Example 208)
[0530] A positive resist solution was prepared in the same manner as in Example 201 except that a 6 mass % propylene glycol monomethyl ether acetate (PGMEA) solution of the resin Ph was used.
[0531] (Example 209)
[0532] A negative resist solution was prepared in the same manner as in Example 201 except that a 6 mass % propylene glycol monomethyl ether acetate (PGMEA) solution of the resin Pi was used.
[0533] (Example 201C)
[0534] A positive resist solution was prepared in the same manner as in Example 201 except that a 6 mass % propylene glycol monomethyl ether acetate (PGMEA) solution of the resin Pj was used.
[0535] (Example 202C)
[0536] A positive resist solution was prepared in the same manner as in Example 201 except that a 6 mass % propylene glycol monomethyl ether acetate (PGMEA) solution of the resin Pk was used.
[0537] (Example 203C)
[0538] A positive resist solution was prepared in the same manner as in Example 201, except that a 6 mass % propylene glycol monomethyl ether acetate (PGMEA) solution of resin P1 was used.
[0539] (Example 204C)
[0540] A positive resist solution was prepared in the same manner as in Example 201 except that a 6 mass % propylene glycol monomethyl ether acetate (PGMEA) solution of the resin Pm was used.
[0541] (Example 205C)
[0542] A positive resist solution was prepared in the same manner as in Example 201 except that a 6 mass % propylene glycol monomethyl ether acetate (PGMEA) solution of the resin Pn was used.
[0543] (Example 206C)
[0544] A positive resist solution was prepared in the same manner as in Example 201 except that a 6 mass % propylene glycol monomethyl ether acetate (PGMEA) solution of the resin Po was used.
[0545] (Example 207C)
[0546] A positive resist solution was prepared in the same manner as in Example 201 except that a 6 mass % propylene glycol monomethyl ether acetate (PGMEA) solution of the resin Pp was used.
[0547] (Example 208C)
[0548] A negative resist solution was prepared in the same manner as in Example 201 except that a 6 mass % propylene glycol monomethyl ether acetate (PGMEA) solution of the resin Pq was used.
[0549] The components of the resins used in Examples 201 to 209 and 201C to 208C are shown in Tables 7-1 and 7-2.
[0550] [Table 7-1]
[0551]
[0552] [Table 7-2]
[0553]
[0554] (2) Anti-corrosion liquid coating process
[0555] The resist solutions of Examples 201 to 209 and 201C to 208C were spin-coated on a 6-inch quartz glass substrate having a 100 nm thick chromium vapor-deposited film, and then heated at 120° C. for 30 minutes to obtain a substrate having a 100 nm thick resist film formed thereon. Two such substrates were prepared.
[0556] (3) Electron beam irradiation process
[0557] For one of the substrates prepared in (2), electron beam irradiation was performed with a spot beam at an acceleration voltage of 50 kV to form a line:space = 1:1 pattern. Then, after immersion in methyl isobutyl ketone / isopropyl alcohol = 85 / 15 (volume ratio) at 25°C for 1 minute, it was rinsed with isopropyl alcohol for 30 seconds, heated at 100°C for 10 minutes, and post-baked. The resulting pattern was observed using a scanning electron microscope, and the irradiation energy when resolving a line with a line width of 50 nm (line:space = 1:1) was taken as the sensitivity. Using the irradiation energy that shows the sensitivity, the minimum size at which a line:space = 1:1 pattern can be resolved using a scanning electron microscope was observed as the resolution. The results are shown in Table 8.
[0558] (4) Evaluation of dry etching resistance
[0559] One of the substrates prepared in (2) was dry-etched using a parallel plate reactive ion etching apparatus in a mixed gas of Cl2 (50 sccm) and O2 (50 sccm) at a temperature of 23°C. The dry etching selectivity (= etching rate of the chromium vapor-deposited film / etching rate of the resist film) was determined, with 1.5 or more being designated as A and less than 1.5 being designated as B. The results are shown in Table 8.
[0560] [Table 8]
[0561]
[0562] Since the resins forming the resist films of the substrates of Examples 201 to 209 all contain repeating units (a) having a partial structure represented by the general formula (I) or (II), the selectivity ratios are large and the substrates show good dry etching resistance. However, since the resins forming the resist films of the substrates of Examples 201C to 208C all contain no repeating units (a), the selectivity ratios are small and the dry etching resistance is insufficient.
[0563] From the above, it can be said that the resin forming the resist film containing the repeating unit (a) is effective in improving the dry etching resistance of the resist film.
[0564] In addition, the present invention is not limited to the above-mentioned embodiments, and various modifications can be made in the implementation stage without departing from the scope of the main purpose. Furthermore, the above-mentioned embodiments include various inventions, and various inventions can be extracted by selecting combinations from the multiple components disclosed. For example, even if several components are deleted from all the components shown in the embodiments, when the technical problem can be solved and the effect can be obtained, the structure without the components can also be extracted as an invention.
[0565] The resist composition of the present embodiment is expected to have a significant effect on improving productivity and quality in the production of photomasks or the production of LSIs and ultra LSIs.
[0566] 《Third Implementation Mode》
[0567] <Synthesis of Polyols>
[0568] 19 types of polyols were synthesized and designated as Pa to Pp. The structural formula of the repeating unit contained in the polyols Pa to Pp will be disclosed later. In addition, the synthesis method of each will be described below.
[0569] Synthesis Example 1: Synthesis of Polyol Pa
[0570] 80 parts by mass of cyclohexanone were prepared as a polymerization solvent. In addition, 5 parts by mass of 2-hydroxyethyl methacrylate (HEMA), 14 parts by mass of methyl methacrylate (MMA), and 1 part by mass of 4-methoxyphenyl methacrylate (MPhMA) were prepared as acrylic acid monomers. Furthermore, 0.22 parts by mass of benzoyl peroxide (BPO) was prepared as a polymerization initiator. They were placed in a reaction vessel provided with a stirring device and a reflux tube, and nitrogen was introduced into the reaction vessel while heating to 80° C., and stirring and refluxing were performed for 8 hours. Thus, a polymer solution of an acrylic acid copolymer formed by repeating units derived from HEMA, repeating units derived from MMA, and repeating units derived from MPhMA was obtained. The obtained polymer solution was added dropwise to a large amount of methanol for reprecipitation purification, and dried under reduced pressure at room temperature for 24 hours to obtain polyol Pa.
[0571] Synthesis Example 2: Synthesis of polyol Pb
[0572] Regarding Synthesis Example 1, polyol Pb was obtained by the same method as in Synthesis Example 1 except that 4-hydroxyphenyl methacrylate (HPMA) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0573] Synthesis Example 3: Synthesis of Polyol Pc
[0574] In Synthesis Example 2, a polyol Pc was obtained by the same method as in Synthesis Example 2 except that 2-hydroxyethyl methacrylate (HEMA) was changed to 5.6 parts by mass and 4-hydroxyphenyl methacrylate (HPMA) was changed to 0.4 parts by mass.
[0575] Synthesis Example 4: Synthesis of polyol Pd
[0576] In Synthesis Example 2, polyol Pd was obtained by the same method as in Synthesis Example 2 except that 2-hydroxyethyl methacrylate (HEMA) was changed to 4 parts by mass and 4-hydroxyphenyl methacrylate (HPMA) was changed to 2 parts by mass.
[0577] Synthesis Example 5: Synthesis of Polyol Pe
[0578] Regarding Synthesis Example 1, a polyol Pe was obtained by the same method as in Synthesis Example 1 except that 4-hydroxyphenylmethacrylamide (HPMAA) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0579] Synthesis Example 6: Synthesis of Polyol Pf
[0580] Regarding Synthesis Example 1, a polyol Pf was obtained by the same method as Synthesis Example 1 except that 4-hydroxyphenylmaleimide (HPhMI) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0581] Synthesis Example 7: Synthesis of polyol Pg
[0582] Regarding Synthesis Example 1, a polyol Pg was obtained by the same method as Synthesis Example 1 except that 2,6-di-tert-butylphenyl methacrylate (t-BuPhMA) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0583] Synthesis Example 8: Synthesis of polyol Ph
[0584] Regarding Synthesis Example 1, a polyol Ph was obtained by the same method as Synthesis Example 1 except that 2,6-di-tert-butyl-4-methoxyphenyl methacrylate (t-BuMPhMA) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0585] Synthesis Example 9: Synthesis of Polyol Pi
[0586] 80 parts by mass of cyclohexanone were prepared as a polymerization solvent. In addition, 5 parts by mass of 2-hydroxyethyl methacrylate (HEMA), 14 parts by mass of methyl methacrylate (MMA), and 1 part by mass of 4-acetoxystyrene (AcSt) were prepared as acrylic acid monomers. Furthermore, 0.22 parts by mass of benzoyl peroxide (BPO) were prepared as a polymerization initiator. They were placed in a reaction vessel provided with a stirring device and a reflux tube, while nitrogen was introduced into the reaction vessel, while heating to 80°C, stirring and refluxing for 8 hours. Thus, a polymer solution of an acrylic acid copolymer formed by repeating units derived from HEMA, repeating units derived from MMA, and repeating units derived from AcSt was obtained. The obtained polymer solution was added dropwise to a large amount of methanol for reprecipitation purification, and dried under reduced pressure at room temperature for 24 hours to obtain a HEMA / MMA / AcSt copolymer. 2 parts by mass of 1mol / l sodium hydroxide ethanol solution and 10 parts by mass of tetrahydrofuran were added to 1 part by mass of the obtained HEMA / MMA / AcSt copolymer and stirred for 2 hours. This solution was added dropwise into a large amount of methanol to obtain polyol Pi.
[0587] Synthesis Example 10: Synthesis of polyol Pj
[0588] Regarding Synthesis Example 1, a polyol Pj was obtained by the same method as Synthesis Example 1 except that 6 parts by mass of 2-hydroxyethyl methacrylate (HEMA) was used and 4-methoxyphenyl methacrylate (MPhMA) was not used.
[0589] Synthesis Example 11: Synthesis of Polyol Pk
[0590] Regarding Synthesis Example 1, a polyol Pk was obtained by the same method as Synthesis Example 1 except that styrene (St) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0591] Synthesis Example 12: Synthesis of Polyol P1
[0592] In Synthesis Example 1, polyol P1 was obtained by the same method as in Synthesis Example 1 except that phenyl methacrylate (PhMA) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0593] Synthesis Example 13: Synthesis of polyol Pm
[0594] Regarding Synthesis Example 1, a polyol Pm was obtained by the same method as in Synthesis Example 1 except that phenylmethacrylamide (PhMAA) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0595] Synthesis Example 14: Synthesis of Polyol Pn
[0596] Regarding Synthesis Example 1, a polyol Pn was obtained by the same method as Synthesis Example 1 except that phenylmaleimide (PhMI) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0597] Synthesis Example 15: Synthesis of Polyol Po
[0598] Regarding Synthesis Example 1, a polyol Po was obtained by the same method as in Synthesis Example 1 except that 4-methoxystyrene (MSt) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0599] Synthesis Example 16: Synthesis of Polyol Pp
[0600] Regarding Synthesis Example 1, a polyol Pp was obtained by the same method as Synthesis Example 1 except that 2,4,6-trimethylstyrene (TMSt) was used instead of 4-methoxyphenyl methacrylate (MPhMA).
[0601] [Chemical structure formula 11-1]
[0602]
[0603] [Chemical structure formula 11-2]
[0604]
[0605] <Production of Gas Barrier Laminated Film>
[0606] The gas barrier multilayer films of Examples 301 to 311 and Examples 301C to 308C were produced in the order of the following steps (1) to (6).
[0607] (1) Preparation process of primer solution
[0608] (Example 301)
[0609] A solution of a methyl ethyl ketone solution of polyol Pa adjusted to a solid content concentration of 5% and a methyl ethyl ketone solution of an isocyanate compound adjusted to a solid content concentration of 5% was prepared in a ratio of 7:3. As the isocyanate compound, an adduct of toluene diisocyanate (Coronate T-65 manufactured by Tosoh Corporation) was used.
[0610] (Example 302)
[0611] The primer layer solution was prepared in the same manner as in Example 301 except that the methyl ethyl ketone solution of polyol Pb adjusted to a solid content concentration of 5% was used.
[0612] (Example 303)
[0613] A methyl ethyl ketone solution of polyol Pb adjusted to a solid content concentration of 5% was mixed with a methyl ethyl ketone solution of an isocyanate compound adjusted to a solid content concentration of 5% in a ratio of 7:3, and then 1 mass % of a light stabilizer (manufactured by BASF Japan Co., Ltd., Tinuvin (registered trademark) 292) was mixed as an additive to form a solid content. The primer layer solution was prepared in the same manner as in Example 301.
[0614] (Example 304)
[0615] The primer layer solution was prepared in the same manner as in Example 301 except that the methyl ethyl ketone solution of polyol Pc adjusted to a solid content concentration of 5% was used.
[0616] (Example 305)
[0617] A primer layer solution was prepared in the same manner as in Example 301 except that a methyl ethyl ketone solution of polyol Pd adjusted to a solid content concentration of 5% was used.
[0618] (Example 306)
[0619] The primer layer solution was prepared in the same manner as in Example 301 except that the methyl ethyl ketone solution of the polyol Pe adjusted to a solid content concentration of 5% was used.
[0620] (Example 307)
[0621] A methyl ethyl ketone solution of a polyol Pe adjusted to a solid content concentration of 5% was mixed with a methyl ethyl ketone solution of an isocyanate compound adjusted to a solid content concentration of 5% in a ratio of 7:3, and then 1 mass % of a light stabilizer (Tinuvin 292 manufactured by BASF Japan Co., Ltd.) was mixed as an additive based on the solid content. The primer layer solution was prepared in the same manner as in Example 301.
[0622] (Example 308)
[0623] A primer layer solution was prepared in the same manner as in Example 301 except that the methyl ethyl ketone solution of the polyol Pf adjusted to a solid content concentration of 5% was used.
[0624] (Example 309)
[0625] A primer layer solution was prepared in the same manner as in Example 301 except that a methyl ethyl ketone solution of polyol Pg adjusted to a solid content concentration of 5% was used.
[0626] (Example 310)
[0627] The primer layer solution was prepared in the same manner as in Example 301 except that a methyl ethyl ketone solution of polyol Ph adjusted to a solid content concentration of 5% was used.
[0628] (Example 311)
[0629] The primer layer solution was prepared in the same manner as in Example 301 except that the methyl ethyl ketone solution of polyol Pi adjusted to a solid content concentration of 5% was used.
[0630] (Example 301C)
[0631] The primer layer solution was prepared in the same manner as in Example 301 except that the methyl ethyl ketone solution of the polyol Pj adjusted to a solid content concentration of 5% was used.
[0632] (Example 302C)
[0633] The primer layer solution was prepared in the same manner as in Example 301 except that the methyl ethyl ketone solution of the polyol Pk adjusted to a solid content concentration of 5% was used.
[0634] (Example 303C)
[0635] The primer layer solution was prepared in the same manner as in Example 301 except that a methyl ethyl ketone solution of polyol P1 adjusted to a solid content concentration of 5% was used.
[0636] (Example 304C)
[0637] A methyl ethyl ketone solution of polyol P1 adjusted to a solid content concentration of 5% was mixed with a methyl ethyl ketone solution of an isocyanate compound adjusted to a solid content concentration of 5% in a ratio of 7:3, and then 1 mass % of a light stabilizer (manufactured by BASF Japan Co., Ltd., Tinuvin 292) was mixed as an additive based on the solid content. The primer layer solution was prepared in the same manner as in Example 301.
[0638] (Example 305C)
[0639] The primer layer solution was prepared in the same manner as in Example 301 except that the methyl ethyl ketone solution of the polyol Pm adjusted to a solid content concentration of 5% was used.
[0640] (Example 306C)
[0641] A primer layer solution was prepared in the same manner as in Example 301 except that a methyl ethyl ketone solution of polyol Pn adjusted to a solid content concentration of 5% was used.
[0642] (Example 307C)
[0643] The primer layer solution was prepared in the same manner as in Example 301 except that the methyl ethyl ketone solution of the polyol Po adjusted to a solid content concentration of 5% was used.
[0644] (Example 308C)
[0645] The primer layer solution was prepared in the same manner as in Example 301 except that the methyl ethyl ketone solution of the polyol Pp adjusted to a solid content concentration of 5% was used.
[0646] Table 9 shows the components of the polyols and the contents of the additives used in Examples 301 to 311 and Examples 301C to 308C.
[0647] [Table 9-1]
[0648] Table 9
[0649]
[0650] [Table 9-2]
[0651] Table 9 (continued)
[0652]
[0653] [Table 9-3]
[0654] Table 9 (continued)
[0655]
[0656] (2) Primer solution coating process
[0657] As the resin substrate, a biaxially stretched PET film (Toray Film Processing Co., Ltd., P60) with a thickness of 12 μm and corona treated on one side was used. The primer layer solutions of Examples 301 to 311 and Examples 301C to 308C were applied to the corona treated surface of the resin substrate using a gravure coater so that the thickness after drying reached 0.20 μm, thereby laminating the primer layer.
[0658] (3) Lamination process of vapor deposited film layers
[0659] A material in which metallic silicon powder and silicon dioxide powder are mixed so that the element ratio O / Si reaches 1.5 is prepared, and a vapor-deposited film layer with a thickness of 0.05 μm is stacked on the primer layer using a vacuum vapor deposition machine to prepare gas barrier laminate films of Examples 301 to 311 and Examples 301C to 308C having a resin substrate / primer layer / vapor-deposited film layer structure.
[0660] (4) Preparation step of gas barrier coating layer solution
[0661] A solution of tetraethoxysilane hydrolyzed with 0.02 mol / L hydrochloric acid was added to a 5% aqueous solution of PVA having a saponification degree of 99% and a polymerization degree of 2400 at a ratio of SiO2 / PVA=60 / 40 to prepare a gas barrier coating layer solution.
[0662] (5) Gas barrier coating layer solution coating step
[0663] The gas barrier coating layer solution is applied onto the vapor-deposited film layer of the gas barrier laminated films of Examples 301 to 311 and Examples 301C to 308C produced in step (3) using a gravure coater, and a gas barrier coating layer having a thickness of 0.40 μm after drying is laminated to produce the gas barrier laminated films of Examples 301 to 311 and Examples 301C to 308C.
[0664] (6) Step of laminating the laminating resin layer on the gas barrier laminate film
[0665] By dry lamination method through 5g / m 2 A polyurethane-based adhesive is used to laminate a 50 μm thick hydrolysis-resistant PET (manufactured by Toray Film Processing Co., Ltd., X10S) on both sides of the gas barrier laminated films of Examples 301 to 311 and Examples 301C to 308C laminated with a gas barrier coating layer produced in step (5) to produce the gas barrier laminated films of Examples 301 to 311 and Examples 301C to 308C.
[0666] <Evaluation of Gas Barrier Laminated Film> (1) Measurement of Water Vapor Permeability
[0667] The gas barrier laminate films of Examples 301 to 311 and Examples 301C to 308C prepared in step (3) were measured for their water vapor permeability (g / m2) in an atmosphere of 40°C and 90% RH using a water vapor permeability meter (MOCON PERMATRAN-W 3 / 31) manufactured by Modern Control. 2 The results are shown in Table 10.
[0668] (2) Implementation of high temperature test
[0669] The gas barrier multilayer films of Examples 301 to 311 and Examples 301C to 308C produced in step (6) were cut into 10 mm widths and subjected to a high temperature test under the temperature and time conditions of the heat resistance test described in JISC 8917.
[0670] (3) Implementation of light resistance test
[0671] The gas barrier multilayer films of Examples 301 to 311 and Examples 301C to 308C after the high temperature test were subjected to a light resistance test. The light resistance test was conducted under conditions such that the irradiation time was set to 120 hours in the light irradiation test described in JISC 8917.
[0672] (4) Determination of adhesion strength
[0673] Using a universal tensile machine type universal tester, the gas barrier laminated films of Examples 301 to 311 and 301C to 308C after only the high temperature test, and the gas barrier laminated films of Examples 301 to 311 and 301C to 308C after both the high temperature test and the light resistance test were subjected to the measurement of the adhesion strength. Specifically, the T-time peel test and the 180-degree peel test as the JISK 6854 test method were carried out to measure the lamination strength (N / 10mm width). In both the T-time peel test and the 180-degree peel test, the lamination strength (adhesion strength) was 1N / 10mm width or more as qualified "A", and the case of less than 1N / 10mm width was unqualified "B". The results are shown in Table 10.
[0674] [Table 10]
[0675]
[0676] Since the polyols forming the primer layer 12 of Examples 301 to 311 all contain repeating units (a) having a partial structure represented by general formula (I) or (II), the gas barrier laminated films all have a close adhesion strength of 1N / 10mm width or more even after a high temperature test. However, since the polyols forming the primer layer 12 of Examples 301C to 308C all do not contain repeating units (a), the close adhesion strength after a high temperature test is less than 1N / 10mm width.
[0677] In addition, the gas barrier laminate film of Example 302 had a reduced adhesion strength after the light resistance test and became unqualified, while the gas barrier laminate film of Example 303, which was produced under the same conditions except that a light stabilizer was added when the primer layer solution was prepared, had an adhesion strength within the qualified range even after the light resistance test. In addition, when comparing Examples 306 and 307, only Example 307, which used a light stabilizer, had an adhesion strength within the qualified range after the light resistance test. However, even in Example 304C, which used the same light stabilizer, the adhesion strength was still insufficient and unqualified during the high temperature test because the polyol forming the primer layer 12 did not contain repeating units (a). This is because the thermal degradation of the light stabilizer as an additive is suppressed by using a polyol containing repeating units (a).
[0678] From the above, it can be seen that the polyol forming the primer layer containing the repeating unit (a) is useful for improving the adhesion of the gas-barrier multilayer film.
[0679] The gas barrier film laminate of the present embodiment is expected to be preferably used in the fields of packaging of foods, daily necessities, and pharmaceuticals, and in the fields of electronic device-related components, particularly when high durability is required.
[0680] 《Fourth Implementation Mode》
[0681] (Example 401)
[0682] A polyester film having a thickness of 12 μm was used as a substrate film 101. A coating solution containing an acrylic polyol containing a partial structure derived from 20 mol% of 4-hydroxyphenyl methacrylate, a TDI-based curing agent as an isocyanate, and γ-isocyanatepropyltrimethoxysilane as a silane coupling agent was applied to the substrate film 101, and then heated and dried to form a primer layer 102 having a thickness of 1 μm. Next, silicon oxide was vapor-deposited on the primer layer 102 to form a silicon oxide vapor-deposited layer 103 having a thickness of 200 nm. Next, a coating solution containing tetramethoxysilane, 1,3,5-tris(3-trimethoxysilylpropyl)isocyanurate, and PVA was applied to the silicon oxide vapor-deposited layer 103, and heated to condense the silicon compound while drying to form a gas barrier coating layer 104 having a thickness of 1 μm. Hereinafter, in order to distinguish it from a comparative film described later, this film is referred to as a "silicon-based gas barrier film".
[0683] Next, an adhesive (Mitsui Chemicals, Inc. dry laminating adhesive, trade name: A525) was applied to the silicon-based gas barrier film using a dry laminator, and a 70 μm thick polyolefin-based unstretched coextruded film (Mitsui Chemicals Tohcell Co., Ltd., trade name: RXC22) was attached as a hot melt adhesive layer 105 to produce a laminate. Next, the laminates were overlapped and heat-sealed around to produce a three-side sealed bag for heat sterilization having a length of 125 mm and a width of 95 mm.
[0684] (Example 402)
[0685] In Example 401, a silicon-based gas barrier film and a three-side sealed bag for heat sterilization were produced by the same method as in Example 401, except that a compound having a partial structure derived from phenyl methacrylate was used as the acrylic polyol instead of the partial structure derived from 4-hydroxyphenyl methacrylate.
[0686] (Example 403)
[0687] In Example 401, a silicon-based gas barrier film and a three-side sealed bag for heat sterilization were produced by the same method as in Example 401, except that a compound having a partial structure derived from 4-hydroxyphenylmethacrylamide was used as the acrylic polyol instead of the partial structure derived from 4-hydroxyphenyl methacrylate.
[0688] (Example 404)
[0689] An adhesive (Mitsui Chemicals, Inc. dry laminating adhesive, trade name: A525) was applied to the silicon-based gas barrier film of Example 401 using a dry laminator, and a polyamide film (Kohjin Co., Ltd., trade name: Bonyl W) having a thickness of 15 μm was laminated thereto. Furthermore, an adhesive (Mitsui Chemicals, Inc. dry laminating adhesive, trade name: A525) was applied to the polyamide film using a dry laminator, and a polyolefin-based unstretched coextruded film (Mitsui Chemicals Tohcell Co., Ltd., trade name: RXC22) having a thickness of 70 μm was laminated thereto as a hot melt adhesive layer 105 to produce a laminate. Subsequently, the laminates were overlapped and the peripheries were heat-sealed to produce a three-side sealed bag for heat sterilization having a length of 125 mm and a width of 95 mm.
[0690] (Example 401C)
[0691] In Example 401, a silicon-based gas barrier film and a three-side sealed bag for heat sterilization were produced by the same method as in Example 401, except that a compound having a partial structure derived from styrene was used as the acrylic polyol instead of the partial structure derived from 4-hydroxyphenyl methacrylate.
[0692] (Example 402C)
[0693] In Example 401, a silicon-based gas barrier film and a three-side sealed bag for heat sterilization were manufactured using the same method as in Example 401, except that a compound having a partial structure derived from hydroxyethyl methacrylate was used as the acrylic polyol instead of the partial structure derived from 4-hydroxyphenyl methacrylate.
[0694] (Example 403C)
[0695] In Example 401, aluminum oxide was deposited on the primer layer 102 to form an aluminum oxide deposited layer with a thickness of 200 nm. Next, a coating liquid containing a metal alkoxide and a water-soluble polymer having a hydroxyl group was applied to the aluminum oxide deposited layer, and the metal alkoxide was condensed while being dried by heating to form a gas barrier coating layer 104 with a thickness of 1 μm. Hereinafter, this film is referred to as an "aluminum-based gas barrier film".
[0696] Next, an adhesive (Mitsui Chemicals, Inc. dry laminating adhesive, trade name: A525) was applied to the aluminum gas barrier film using a dry laminator, and a 70 μm thick polyolefin non-stretched coextruded film (Mitsui Chemicals Tohcell Co., Ltd., trade name: RXC22) was attached as a hot melt adhesive layer 105 to produce a laminate. Next, the laminates were overlapped and heat-sealed around to produce a three-side sealed bag for heat sterilization having a length of 125 mm and a width of 95 mm.
[0697] (Example 404C)
[0698] An adhesive (Mitsui Chemicals, Inc. dry laminating adhesive, trade name: A525) was applied to the aluminum gas barrier film using a dry laminator, and a 15 μm thick polyamide film (Kohjin Co., Ltd., trade name: Bonyl W) was laminated thereto. Furthermore, an adhesive (Mitsui Chemicals, Inc. dry laminating adhesive, trade name: A525) was applied to the polyamide film using a dry laminator, and a 70 μm thick polyolefin-based unstretched coextruded film (Mitsui Chemicals Tohcell Co., Ltd., trade name: RXC22) was laminated thereto as a hot melt adhesive layer 105 to produce a laminate. Next, the laminates were overlapped and the periphery was heat-sealed to produce a three-side sealed bag for heat sterilization having a length of 125 mm and a width of 95 mm.
[0699] (evaluate)
[0700] 50 ml of pure water was sealed in the three-side sealed bags for heat sterilization of Examples 401 to 404 and Examples 401C to 404C, and high-temperature and high-pressure sterilization was performed at a temperature of 130°C and a time of 30 minutes using a high-temperature and high-pressure treatment device (manufactured by Nissaka Manufacturing Co., Ltd., product name: RCS-40RTG.N).
[0701] Furthermore, the oxygen barrier property and water vapor barrier property before and after high temperature and high pressure sterilization were evaluated as follows. In addition, the bag breaking strength after high temperature and high pressure sterilization was evaluated by pressure resistance test and drop test. Furthermore, the adhesion between the substrate and the inorganic vapor-deposited layer was visually evaluated for the presence or absence of interlayer peeling after high temperature and high pressure sterilization. The results are shown in Table 11.
[0702] The oxygen barrier property is evaluated by measuring the oxygen permeability by the Mocon method according to JIS K7126 under the conditions of temperature 30°C and humidity 70% RH. In addition, the water vapor barrier property is evaluated by measuring the water vapor permeability by the Mocon method according to JIS K7129 under the conditions of temperature 40°C and humidity 90% RH. A low value in both cases means excellent barrier properties.
[0703] The pressure test is to apply a load of 80 kg to the three-side sealed bags after high temperature and high pressure sterilization for 1 minute, and count the number of bags that are broken. The drop test is to store the three-side sealed bags after high temperature and high pressure sterilization in a refrigerator at 5°C for 24 hours, and then drop them twice from a height of 80 cm in such a way that the flat part of the three-side sealed bags touches the concrete floor, and count the number of bags that are broken. For each test, the number of samples is 5, and "0 / 5" in the table means that there is no bag broken.
[0704] The delamination was observed by bending the sealed portion of the small bag 180 degrees after the high temperature and high pressure sterilization treatment. The visual observation results were as follows: B indicated the case where the inorganic oxide vapor deposited layer was delaminated from the substrate film, and A indicated the case where no delamination was observed.
[0705] [Table 11]
[0706]
[0707] As can be seen from the results of Table 11, no significant difference was observed between Examples 401 to 404 and Examples 401C to 404C in terms of the pressure resistance test and the drop test. All of them had excellent bag breaking strength. In addition, no significant difference was observed between Examples 401 to 404 and Examples 401C to 404C in terms of oxygen barrier properties before and after high temperature and high pressure sterilization.
[0708] On the other hand, the water vapor barrier properties of the three-side sealed bags of Examples 403C to 404C were significantly reduced after high temperature and high pressure sterilization, but the three-side sealed bags of Examples 401 to 404 and Examples 401C to 402C maintained high barrier properties after high temperature and high pressure sterilization.
[0709] In the evaluation of interlayer delamination, delamination between the base film and the inorganic oxide vapor-deposited layer was observed in Examples 401C to 402C.
[0710] From these results, it can be seen that the packaging bag of this embodiment maintains excellent bag breaking strength and oxygen barrier properties before and after high temperature and high pressure sterilization, and at the same time greatly improves the water vapor barrier properties after high temperature and high pressure sterilization, and the adhesion between the substrate and the inorganic vapor-deposited layer is good.
[0711] 《Fifth Implementation Mode》
[0712] The performance of the hard coating film of the present embodiment was evaluated by the following method.
[0713] Haze: The haze (%) of the hard coating film was determined by measuring using NDH-2000 manufactured by Nippon Denshoku Co., Ltd. in accordance with JIS-K7105.
[0714] Total light transmittance: The transmittance (%) of the hard coating film was determined by measuring the total light transmittance using NDH-2000 manufactured by Nippon Denshoku Co., Ltd. in accordance with JIS-K7105.
[0715] Pencil hardness: The hardness of the hard coating layer of the hard coating film was determined by evaluation in accordance with JIS-K5400.
[0716] Scratch resistance: Apply 250g / cm2 of #0000 steel wool to the hard coating of the hard coating. 2Repeat 10 times with a load to check whether there are any scratches. The judgment criteria are as follows.
[0717] A: No scars
[0718] B: There are scars
[0719] Antifouling properties: A fingerprint was placed on the hard coating surface of the hard coating film, and a cellulose nonwoven fabric (BEMCOT M-3: manufactured by Asahi Kasei Corporation) was applied at 250 g / cm 2 The fingerprints were wiped off with a load and the ease of removal was determined visually. The determination criteria are as follows.
[0720] A: Fingerprints can be completely wiped off
[0721] B: Fingerprint wipe marks remain
[0722] C: Cannot wipe fingerprints
[0723] Surface energy: Use a contact angle meter (CA-X type: Kyowa Interface Science Co., Ltd.) to make a droplet with a diameter of 1.8 mm in a dry state (20°C-65% RH) at the tip of a needle, and make it contact the surface of the hard coating to make a droplet. The contact angle refers to the angle between the tangent line to the liquid surface and the solid surface at the point where the solid and liquid are in contact, and is defined by the angle on the side that includes the liquid. Distilled water and n-hexadecane were used as liquids, respectively. The contact angles of the two solutions were calculated using the extended Fowkes calculation formula.
[0724] Heat resistance: After forming a coating film of the hard coating forming composition on a glass substrate, a few mg or so is cut out from the glass substrate and sealed in an aluminum pan, and the mass reduction rate (%) under a nitrogen atmosphere is measured using the following method. The mass reduction rate (%) is measured using a differential thermogravimetric simultaneous measurement device (STA7000, manufactured by Hitachi High-TechScience Co., Ltd.). The sample is heated at 250°C for 20 minutes under a nitrogen atmosphere, and the mass reduction (M=M0-M1) obtained by subtracting the mass after heating (M1) from the initial mass before heating (M0) is divided by the initial mass (M0) to calculate the mass reduction rate ([M / M0]×100) (%). The lower the mass reduction rate, the better the heat resistance.
[0725] Thermal degradation of additives: 0.1 parts by mass of a hindered amine light stabilizer (trade name: Tinuvin (Tinuvin (registered trademark)) 123, manufactured by BASF Japan Co., Ltd.) was added as an additive to the hard coat layer forming composition to form a hard coat layer with the light stabilizer added on a glass substrate. The glass substrate with the coating film formed thereon was heated at 250°C for 10 minutes, and the residual rate of the additive in the coating film was measured by the following method. The glass substrate was placed at 1 cm 2 The glass substrate was cut into pieces of different sizes, immersed in 1.5 mL of acetone, and extracted in an ultrasonic washing machine for 60 minutes. The additives in the glass substrate extract were quantitatively analyzed using ultra-high performance liquid chromatography / mass spectrometry (UHPLC / MS) (ultra-high performance liquid chromatography / mass spectrometry (UHPLC / MS), Agilent 1260LC System / 6130B Single Quad MS System). The residual additive rate ([V1 / V0]×100) (%) was calculated by dividing the residual additive amount (V1) after heating by the initial additive amount (V0) before heating.
[0726] The hard coating films of Examples 501 to 504 and Examples 501C to 504C were used in the above evaluations. Hereinafter, the methods for producing these hard coating films will be described.
[0727] <Example 501>
[0728] A cellulose triacetate film substrate with a thickness of 80 μm was used as a transparent substrate. A coating solution in which the following components were stirred and mixed was applied to the substrate by a bar coating method so that the cured film thickness was 12 μm and dried. Next, the substrate was irradiated with a metal halide lamp at 400 mJ / cm 2 The ultraviolet rays were applied to form a hard coating layer, thereby producing a hard coating film of Example 501. The measurement results of the total light transmittance, haze, scratch resistance test, pencil hardness, antifouling properties, and heat resistance of the hard coating film are shown in Table 12.
[0729] The ingredients shown above are as follows:
[0730] Urethane acrylate: dipentaerythritol pentaacrylate hexamethylene diisocyanate urethane
[0731]
[0732] <Example 502>
[0733] A cellulose triacetate film substrate with a thickness of 80 μm was used as a transparent substrate. A coating solution in which the following components were stirred and mixed was applied to the substrate by a bar coating method so that the cured film thickness was 12 μm and dried. Next, the substrate was irradiated with a metal halide lamp at 400 mJ / cm2 The ultraviolet rays were applied to form a hard coating layer, thereby producing a hard coating film of Example 502. The measurement results of the total light transmittance, haze, scratch resistance test, pencil hardness, antifouling properties, and heat resistance of the hard coating film are shown in Table 12.
[0734] The ingredients shown above are as follows:
[0735] Urethane acrylate: Pentaerythritol triacrylate Isophorone diisocyanate Amino
[0736]
[0737] <Example 503>
[0738] A cellulose triacetate film substrate with a thickness of 80 μm was used as a transparent substrate. A coating solution in which the following components were stirred and mixed was applied to the substrate by a bar coating method so that the cured film thickness was 12 μm and dried. Next, the substrate was irradiated with a metal halide lamp at 400 mJ / cm 2 The ultraviolet rays were applied to form a hard coating layer, thereby producing a hard coating film of Example 503. The measurement results of the total light transmittance, haze, scratch resistance test, pencil hardness, antifouling properties, and heat resistance of the hard coating film are shown in Table 12.
[0739] The ingredients shown above are as follows:
[0740]
[0741] <Example 504>
[0742] A cellulose triacetate film substrate with a thickness of 80 μm was used as a transparent substrate. A coating solution in which the following components were stirred and mixed was applied to the substrate by a bar coating method so that the cured film thickness was 12 μm and dried. Next, the substrate was irradiated with a metal halide lamp at 400 mJ / cm 2 The ultraviolet rays were applied to form a hard coating layer, thereby producing a hard coating film of Example 504. The measurement results of the total light transmittance, haze, scratch resistance test, pencil hardness, antifouling properties, and heat resistance of the hard coating film are shown in Table 12.
[0743] The ingredients shown above are as follows:
[0744]
[0745] <Example 501C>
[0746] A cellulose triacetate film substrate with a thickness of 80 μm was used as a transparent substrate. A coating solution in which the following components were stirred and mixed was applied to the substrate by a bar coating method so that the cured film thickness was 12 μm and dried. Next, the substrate was irradiated with a metal halide lamp at 400 mJ / cm2 The ultraviolet rays were applied to form a hard coating layer, and a hard coating film of Example 501C was prepared. The measurement results of the total light transmittance, haze, scratch resistance test, pencil hardness, and antifouling properties of the hard coating film are shown in Table 12.
[0747] The ingredients shown above are as follows:
[0748]
[0749] <Example 502C>
[0750] A cellulose triacetate film substrate with a thickness of 80 μm was used as a transparent substrate. A coating solution in which the following components were stirred and mixed was applied to the substrate by a bar coating method so that the cured film thickness was 12 μm and dried. Next, the substrate was irradiated with a metal halide lamp at 400 mJ / cm 2 The ultraviolet rays were applied to form a hard coating layer, and a hard coating film of Example 502C was prepared. The total light transmittance, haze, scratch resistance test, pencil hardness, and antifouling properties of the hard coating film are shown in Table 12.
[0751] The ingredients shown above are as follows:
[0752]
[0753]
[0754] <Example 503C>
[0755] A cellulose triacetate film substrate having a thickness of 80 μm was used as the transparent substrate. The components shown below were stirred, but the coating liquid became cloudy and could not be evaluated.
[0756] The ingredients shown above are as follows:
[0757]
[0758] <Example 504C>
[0759] A cellulose triacetate film substrate having a thickness of 80 μm was used as the transparent substrate. The components shown below were stirred, but the coating liquid became cloudy and could not be evaluated.
[0760] The ingredients shown above are as follows:
[0761]
[0762] The evaluation results of Examples 501 to 504, Example 501C, and Example 502C are summarized in Table 12.
[0763] [Table 12]
[0764]
[0765] In Examples 501 to 504, Example 501C, and Example 502C, since urethane acrylate was used as the polyfunctional (meth)acrylic monomer (A), the pencil hardness of any hard coating film was 3H and the scratch resistance was also good.
[0766] When comparing Examples 501 to 504 with Examples 501C and 502C, the hard coating films of Examples 501 to 504 using a fluorine-containing compound (D) having a polymerizable group have sufficient antifouling properties, a surface energy of less than 20 mN / m, and are good, while Examples 501C and 502C, which do not use a fluorine-containing compound having a polymerizable group, do not exhibit sufficient antifouling properties and have a surface energy of more than 20 mN / m. In addition, by using a monomer (B) having a partial structure represented by the general formula (I) or (II), the mass reduction and deterioration of additives caused by heating can be suppressed. However, in Examples 501C and 502C, it is believed that due to the use of non-polymerizable fluorine-based compounds and non-polymerizable silicone-based compounds, the uniformity of the coating film after photocuring deteriorates, resulting in a portion that is easily degraded by heat, resulting in a high mass reduction rate and a low residual rate. In addition, the case where the mass reduction rate is less than 3% is considered good, and the case where the residual rate is more than 95% is considered good.
[0767] Comparison of Examples 501 to 504 with Examples 503C and 504C shows that the use of a monomer (B) having a partial structure represented by the general formula (I) or (II) improves compatibility with fluorine-based additives.
[0768] In addition, the invention of the present application is not limited to the above-mentioned embodiments, and various modifications can be made in the implementation stage without departing from the scope of its main purpose. In addition, each embodiment can be implemented in combination as much as possible, and a combination effect is obtained in this case. Furthermore, the above-mentioned embodiments include inventions at various stages, and various inventions can be extracted by appropriate combinations of the disclosed multiple constituent elements.
[0769] Explanation of symbols
[0770] 10, 20, 30 gas barrier laminate film, 11 resin substrate, 12 primer layer, 13 vapor-deposited film layer, 21 gas barrier coating layer, 31 adhesive layer, 32 laminated resin layer, 100, 200 laminate (packaging material), 101 substrate film, 102 primer layer, 103 silicon oxide vapor-deposited layer, 104 gas barrier coating layer, 105 hot-melt adhesive layer, 206 polyamide film, ad1, ad2, ad3 adhesive layer, 300 hard coating film, 301 transparent substrate, 302 hard coating layer.
Claims
1. A gas barrier laminate film, The present invention is a gas barrier laminate film comprising a resin substrate, a primer layer and a vapor-deposited film layer, wherein the primer layer and the vapor-deposited film layer are sequentially laminated on at least one surface of the resin substrate, wherein: The primer layer is a layer derived from a resin composition, which comprises a complex of a polyol and an isocyanate compound, wherein the resin composition comprises a resin R having a repeating unit having a partial structure represented by the following general formula (I) or (II), wherein the resin R is the polyol, [Chemical structure 1] In formula (I), Q A The ester bond shown in the formula, R A represents a substituent, n1 represents an integer of 1 to 5, * represents a bonding site with the rest of the repeating unit, ** represents a bonding site with the phenyl group in the formula, and R A The substituent represented by is selected from an alkyl group, a cycloalkyl group, an alkoxy group, an acetyl group, a nitro group, a cyano group, a carboxyl group, an amino group, an ester group, and a halogen atom, [Chemical structure 2] In formula (II), Q B represents the difference between Q in formula (I) A The linking group other than the ester bond shown, R B represents a substituent, n2 represents an integer of 1 to 5, and * represents a bonding site with the rest of the repeating unit, wherein at least one R B represents hydroxyl group, Q B The Q A The linking group other than the ester bond is selected from -CONR-, a urethane bond, and an ether bond, and R in -CONR- represents an alkyl group.
2. The gas barrier multilayer film according to claim 1, wherein The resin composition further contains an additive, and the blending ratio of the additive to the resin R is 50 mass % or less.
3. The gas barrier multilayer film according to claim 1 or 2, wherein The content of the repeating unit in the resin R is 2 mol% or more and 50 mol% or less relative to all the repeating units in the resin R.
4. The gas barrier multilayer film according to claim 1 or 2, wherein The repeating unit is any one of a repeating unit derived from a (meth)acrylate monomer, a repeating unit derived from a (meth)acrylamide monomer, and a repeating unit derived from an N-substituted maleimide monomer.
5. The gas barrier multilayer film according to claim 1 or 2, wherein The resin R further contains, in addition to the repeating units, a (meth)acrylate repeating unit having a linear or branched alkyl group having 1 to 5 carbon atoms in a side chain and / or a (meth)acrylate repeating unit having a hydroxyl group other than a phenolic hydroxyl group in a side chain.
6. The gas barrier multilayer film according to claim 1 or 2, wherein The resin R further contains an olefin-based repeating unit in addition to the repeating unit.
7. The gas barrier multilayer film according to claim 1 or 2, wherein The resin R further contains a halogen atom-containing repeating unit in addition to the repeating unit.
8. The gas barrier multilayer film according to claim 1 or 2, wherein A gas barrier coating layer is provided on the surface of the vapor deposited film layer. The gas barrier coating layer is a dry film formed of a thin film of a coating liquid containing a water-soluble polymer and alkoxysilane or a hydrolyzate thereof.
9. A packaging bag for heat sterilization, The invention discloses a packaging bag for heat sterilization, which is formed by a laminated body in which a base film, a primer layer, a silicon oxide vapor-deposited layer, a gas barrier coating layer, and a heat-melting adhesive layer are laminated in this order, wherein: The primer layer is a layer derived from a resin composition, which comprises a reaction product of an acrylic polyol, an isocyanate and a silane coupling agent, wherein the resin composition comprises a resin R having a repeating unit having a partial structure represented by the following general formula (I) or (II), wherein the resin R is the acrylic polyol. [Chemical structure 1] In formula (I), Q A The ester bond shown in the formula, R A represents a substituent, n1 represents an integer of 1 to 5, * represents a bonding site with the rest of the repeating unit, ** represents a bonding site with the phenyl group in the formula, and R A The substituent represented by is selected from an alkyl group, a cycloalkyl group, an alkoxy group, an acetyl group, a nitro group, a cyano group, a carboxyl group, an amino group, an ester group, and a halogen atom, [Chemical structure 2] In formula (II), Q B represents the difference between Q in formula (I) A The linking group other than the ester bond shown, R B represents a substituent, n2 represents an integer of 1 to 5, and * represents a bonding site with the rest of the repeating unit, wherein at least one R B represents hydroxyl group, Q B The Q A The connecting group other than the ester bond is selected from -CONR-, a carbamate bond, and an ether bond, wherein R in -CONR- represents an alkyl group, The gas barrier coating layer is formed by a dried coating film of a coating liquid containing a silicon compound or a hydrolyzate or condensate thereof and a water-soluble polymer having a hydroxyl group. The silicon compound contains two of the following (a) and (b), The mass of component (a) is converted into SiO2 and the mass of component (b) is converted into R 2 When Si(OH)3, R 2 The solid content of Si(OH)3 is 1 to 50% by mass relative to the total solid content, and the mass of component (a) is converted into SiO2, and the mass of component (b) is converted into R 2 When Si(OH)3 is used, the solid content ratio is SiO2 / (R 2 Si(OH)3+the water-soluble polymer)=100 / 100 to 100 / 30, (a) a silicon compound represented by the following general formula (III) or a hydrolyzate thereof, Si(OR 1 )4(III) In the general formula (III), R 1 represents CH3, C2H5, or C2H4OCH3, (b) a silicon compound represented by the general formula (IV), or a hydrolyzate or condensate thereof, (R 2 Si(OR 3 )3)n(IV) In the general formula (IV), R 2 Represents an organic functional group, R 3 represents CH3, C2H5, or C2H4OCH3, and n represents 1 or more.
10. The packaging bag for heat sterilization according to claim 9, wherein: The resin composition further contains an additive, and the blending ratio of the additive to the resin R is 50 mass % or less.
11. The packaging bag for heat sterilization according to claim 9 or 10, wherein: The content of the repeating unit in the resin R is 2 mol% or more and 50 mol% or less relative to all the repeating units in the resin R.
12. The packaging bag for heat sterilization according to claim 9 or 10, wherein: The repeating unit is any one of a repeating unit derived from a (meth)acrylate monomer, a repeating unit derived from a (meth)acrylamide monomer, and a repeating unit derived from an N-substituted maleimide monomer.
13. The packaging bag for heat sterilization according to claim 9 or 10, wherein: The resin R further contains, in addition to the repeating units, a (meth)acrylate repeating unit having a linear or branched alkyl group having 1 to 5 carbon atoms in a side chain and / or a (meth)acrylate repeating unit having a hydroxyl group other than a phenolic hydroxyl group in a side chain.
14. The packaging bag for heat sterilization according to claim 9 or 10, wherein: The resin R further contains an olefin-based repeating unit in addition to the repeating unit.
15. The packaging bag for heat sterilization according to claim 9 or 10, wherein: The resin R further contains a halogen atom-containing repeating unit in addition to the repeating unit.
16. The packaging bag for heat sterilization according to claim 9 or 10, wherein: The component (b) is a trimer 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate represented by the following general formula (V): (NCO-R 4 Si(OR 3 )3)3(V) In the general formula (V), R 4 Represents (CH2)n, R 3 represents CH3, C2H5, or C2H4OCH3, and n represents 1 or more.
Citation Information
Patent Citations
Antifouling and lowly reflective plastic
JP1986247743A
Transparent plastic having dampproofing
JP1988028017B2
Production of antireflecting article
JP1989086101A
Filter for CRT
JP1992338901A
Stabilized polypropylene resin composition
JP1998338777A